Method for manufacturing circuit component comprising using graphene assembly made by frictionally compressing graphenes with one another as circuit board, frictionally compressing insulating layer to surface of circuit board, and frictionally compressing conductive layer to surface of insulating layer
By friction welding of graphene circuit board and forming a metal oxide nanoparticle insulating layer and a metal nanoparticle conductive layer on it, the problems of insufficient thermal conductivity, heat resistance, mechanical strength and electromagnetic wave shielding of metal-based circuit boards are solved, and low-cost and high-performance circuit board manufacturing is achieved.
Patent Information
- Application Number
- JP2022114436
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-07-18
- Publication Date
- 2025-02-10
AI Technical Summary
Existing metal-based circuit boards have shortcomings in high thermal conductivity, heat resistance, mechanical strength, electromagnetic wave shielding and lightweighting, and traditional methods have high manufacturing costs, making it difficult to achieve large-scale low-cost production.
The circuit board is formed by friction welding using graphene, and an insulating layer composed of metal oxide nanoparticles and a conductive layer composed of metal nanoparticles are formed on its surface. The insulating layer and conductive layer are fixed to the circuit board by friction welding.
It realizes circuit boards with excellent thermal conductivity, heat resistance, mechanical strength and electromagnetic wave shielding. It has a simple manufacturing process and low cost, and is suitable for circuit boards of various sizes and shapes.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a circuit component in which a graphene joint formed by friction welding graphene particles is used as a circuit board, an insulating layer made of an assembly of metal oxide particles formed by friction welding insulating metal oxide particles to a surface of the circuit board, and a conductive layer made of an assembly of metal particles formed by metallic bonding to the surface of the insulating layer is frictionally welded to the surface of the insulating layer, and the insulating layer and the conductive layer are formed on the surface of the circuit board. In the present invention, a substrate used in an electronic circuit is called a circuit board, and a circuit board having an insulating layer and a conductive layer formed on the surface thereof is called a circuit component.
[0002] Here, we will explain graphene. In 2004, a physicist from the University of Manchester in the UK used cellophane tape to peel off a single crystallite from graphite, that is, the basal plane of a graphite crystal that forms a two-dimensional network structure of hexagonal carbon atoms, and succeeded for the first time in extracting a planar material whose thickness is the size of a carbon atom. This new material was called graphene. For this research result, a Nobel Prize in Physics was awarded in 2010. Graphene is a completely new carbon material that is extremely thin, with a thickness equivalent to the size of a carbon atom, and has almost no mass. For this reason, it has properties that are significantly different from those of conventional materials, and is attracting attention as a material that can be used in a wide range of applications. It is the thinnest material with a thickness of 0.332 nm. It also has a surface area of 3000 m per unit mass. 2 / g. It also has a large Young's modulus of 1020 GPa, making it the most stretchable and bendable material. It also has a large shear modulus of 440 GPa, making it the strongest material. Its thermal conductivity is 19.5 W / Cm, which is 4.5 times that of silver, the metal with the highest thermal conductivity. Its current density is more than 1,000 times that of copper. It also has an electron mobility of 15,000 cm. 2 / Volt-sec is the mobility of silicone, 1,400 cm 2 / Volt·sec. Furthermore, it is a single crystal material with a melting point exceeding 3000°C, making it an extremely heat-resistant material. [Background technology]
[0003] In recent years, the problem of heat generation has become more serious in high-speed, large-capacity communication electronic devices, which are rapidly becoming more widespread, circuit boards that pass large currents, and heat-generating components such as power devices and LEDs. In addition, as electronic devices become smaller, lighter, and thinner, how to transfer the heat generated within electronic devices and release it to the outside has become a major issue. Furthermore, due to the high-density mounting, high integration, and high power of electronic components, electronic circuits are required to simultaneously increase the mechanical strength, improve heat resistance, and improve electromagnetic wave shielding, as well as transfer heat in electronic circuits.
[0004] Metal substrates are currently used as circuit boards in order to improve the heat dissipation efficiency of electronic circuits, increase mechanical strength, and also improve heat resistance at the same time. Metal substrates are made by forming an insulating layer of synthetic resin on a metal plate made of aluminum, copper, iron, silicon steel, stainless steel, etc., and then forming a conductive layer on the insulating layer by adhering copper foil, etching the copper foil, applying copper plating, or forming a metal sputtering film or vapor deposition film. However, metal substrates have the following problems. First, the thermal conductivity of the synthetic resin that forms the insulating layer is low. For example, the thermal conductivity of epoxy resin is 0.17-0.21 W / mK, and the ratio of this to the thermal conductivity of copper, 372 W / mK, is 4.6-5.6 × 10 -4 Furthermore, the thickness of the synthetic resin insulating layer is greater than 100 microns. This makes it difficult for the heat generated by the electronic circuit to be transmitted to the metal board. Secondly, the heat resistance of the synthetic resin insulating layer is low, for example, the heat resistance temperature of epoxy resin during continuous use is 100-250° C. Therefore, the withstand voltage of the insulating layer decreases when the electronic circuit generates heat. Thirdly, the mechanical strength of the synthetic resin insulating layer is low. For example, the tensile strength of epoxy resin is 27-89 MPa. Therefore, when a large load is applied to the electronic device, the insulating layer peels off. In addition, the insulating layer is easily peeled off at the heat generating parts of the electronic circuit. Fourth, in order to provide the metal substrate with heat dissipation properties, the metal substrate must have an area necessary for heat dissipation, which increases the weight of the metal substrate and hinders the miniaturization, weight reduction, and thickness reduction of electronic devices.
[0005] Various efforts are being made to address these issues associated with metal substrates. Patent Document 1 describes a method for mounting an LED element on a metal substrate and a metal substrate on which it is mounted. That is, the LED element is mounted directly on the metal surface of the metal substrate to promote heat dissipation and improve the brightness and lifespan of the LED element. For this purpose, the metal substrate is either made flat with wiring and a frame, or one or more truncated cone-shaped recesses with an inverted trapezoidal cross section are made, and the LED element is placed in the truncated cone-shaped recess and fixed and wired, and the upper surface of the element is completely filled with a transparent material, or the inside of the recess is filled with gas and the outside is sealed with a transparent material or a glass plate. On the other hand, the mounting of the LED element on the metal substrate is configured such that the emitted light beam from the LED element toward the side wall of the recess is reflected toward the front direction of the element by the metal surface exposed on the side wall of the recess or the metal coating surface formed on the resin or plating foil on the side wall. Furthermore, glass or organic transparent resin is used as the transparent material. However, in order to mount the LED elements directly on the metal substrate, the mounting of the LED elements as described above must be made complex, and the cost of mounting the LED elements directly on the metal substrate increases. Therefore, this metal substrate is not versatile and is expensive. On the other hand, substrates used for electronic circuits must be versatile and inexpensive.
[0006] Patent Document 2 describes a metal substrate for semiconductor components and a method for manufacturing the same. That is, by using a heat-resistant insulating layer, high electrical conductivity and high heat dissipation are realized, and furthermore, by using a metal thin plate with a thermal expansion coefficient close to that of silicon, it is possible to respond to high integration. For this purpose, SiO 2 , Al 2 O 3 , MgO, ZrO 2 A metal substrate for semiconductor components is manufactured by forming a thin film having a thickness of 0.1 to 1.0 μm and made of an oxide having at least one of the above as a main component. However, Fe-Ni alloy thin plates are expensive, and the manufacturing cost of the metal substrate becomes even more expensive by forming a thin metal oxide film by vapor phase growth. Therefore, the metal substrate is not versatile and is expensive. On the other hand, circuit boards used in electronic circuits must be versatile and inexpensive.
[0007] Here, we summarize the issues related to next-generation circuit components that make up electronic circuits. The circuit boards that make up the circuit components have the following characteristics: First, excellent thermal conductivity. Second, excellent heat resistance. Third, excellent mechanical strength. Fourth, excellent electromagnetic wave shielding. Fifth, lightweight. Next-generation circuit boards will achieve all five of these performance characteristics. On the other hand, a circuit board that achieves all five performances requires a conductive layer and an insulating layer to be formed on the surface of the circuit board. However, as with the problem of metal boards explained in the fourth paragraph, forming an insulating layer with synthetic resin reduces the thermal conductivity, heat resistance, voltage resistance, and mechanical strength of the circuit board. Therefore, sixthly, it is necessary to form the insulating layer with a material other than synthetic resin. Also, as explained in the two patent documents, a circuit board that uses a special material, is manufactured by a special method, and has a special structure is not versatile and is expensive. Therefore, seventhly, a circuit board with a simple structure is manufactured by using inexpensive raw materials and performing simple processing. If these seven challenges can be resolved, the material will become a circuit component for use in next-generation electronic circuits. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2007-158086 A [Patent Document 2] JP 2004-342636 A [Patent Document 3] Patent No. 6166860 Summary of the Invention [Problem to be solved by the invention]
[0009] As described in paragraph 7, there are seven challenges to realizing circuit components for next-generation electronic circuits. Of these, six challenges are related to circuit boards, excluding the sixth challenge. Of these six circuit board challenges, the material closest to solving five challenges excluding the seventh challenge is aluminum. That is, first, aluminum is a metal with excellent thermal conductivity, third after silver, copper, and gold. Second, the melting point of aluminum is 660°C, and its heat resistance as a circuit board is sufficiently high. Third, the tensile strength of pure aluminum is low at 55 MPa, but the tensile strength of an aluminum alloy with trace amounts of magnesium and manganese added is 345 MPa, and its tensile strength as a circuit board is high. On the other hand, there is a correlation between the electromagnetic wave shielding effect and the volume resistivity of a material, and a shielding effect of about 45 dB can be obtained at a volume resistivity of 1 Ω cm. Fourth, the volume resistivity of aluminum is 2.5 μΩ cm, making it the metal with the best shielding effect after silver and copper. Fifth, the density of aluminum is 2.7 g / cm 3 The density of the glass epoxy board (FR-4) is 1.8g / cm 3 Because aluminum has all five of these properties, it is used in metal substrates along with copper. Therefore, the challenges of circuit components to be used in next-generation electronic circuits can be summarized into the following three items. First, it is a circuit board that combines performance superior to the five properties of aluminum. Second, the insulating layer formed on the circuit board does not have the three challenges described in the third paragraph. Therefore, it is necessary to form the insulating layer using a new insulating material and a new manufacturing method. Third, using inexpensive materials, circuit components in which insulating layers and conductive layers are formed with simple structures are manufactured with simple processing. This allows the production of next-generation circuit components that are inexpensive, have a simple structure, and are versatile. As a method for forming next-generation circuit components that solves all of these issues, the inventors have filed a patent application (Japanese Patent Application No. 2020-109143) for using a graphene conjugate as a circuit substrate.
[0010] That is, in the prior application, a graphene joint formed by joining graphene to itself by friction welding is formed on the bottom surface of a container in the shape of the bottom surface, and the graphene joint is used as a circuit board. Also, a metal compound that precipitates a metal oxide upon thermal decomposition is dispersed in methanol, dissolved in methanol, and an organic compound having a higher viscosity than methanol and a boiling point higher than the thermal decomposition temperature of the metal compound is mixed into the methanol dispersion of the metal compound to prepare an insulating paste. Furthermore, a metal compound that precipitates a metal upon thermal decomposition is dispersed in methanol, dissolved in methanol, and an organic compound having a higher viscosity than methanol and a boiling point higher than the thermal decomposition temperature of the metal compound is mixed into the methanol dispersion of the metal compound to prepare a conductive paste. Thereafter, the graphene conjugated body is peeled off from the bottom surface of the container, the insulating paste is applied to the surface of the graphene conjugated body, the graphene conjugated body is placed in a heat treatment device, the metal compound is thermally decomposed to precipitate a collection of fine particles made of insulating metal oxide, the graphene conjugated body is removed from the heat treatment device, the collection of fine particles made of metal oxide is compressed, and the collection of fine particles made of metal oxide is frictionally welded to the graphene conjugated body to form an insulating layer. Furthermore, the conductive paste is applied to the surface of the insulating layer, the graphene conjugated body is placed in a heat treatment device, the metal compound is thermally decomposed to precipitate a collection of fine particles made of conductive metal, the graphene conjugated body is removed from the heat treatment device, the collection of fine particles made of metal is compressed, and the collection of fine particles made of metal is frictionally welded to the insulating layer to form a conductive layer.
[0011] On the other hand, circuit components in which an insulating layer and a conductive layer are formed on a circuit board are general-purpose components, and circuit components of the same size and configuration are mass-produced at low cost. Also, because the uses of circuit components are extremely wide, the size of square circuit boards ranges from 1 cm square to 50 cm square, and some rectangular circuit boards are less than 1 cm wide. Thus, circuit boards come in a variety of sizes and shapes. By the way, the graphene conjugate, which is the thinnest material consisting of graphene with a thickness of 0.332 nm and is formed by friction-welding 20 graphene sheets, has a thickness of only 6.64 nm and has almost no mass. Therefore, when using the graphene conjugate as a circuit board, the smaller the area of the graphene conjugate and the smaller the width of the rectangular graphene conjugate, the more difficult it is to handle the graphene conjugate. Furthermore, in order to mass-produce circuit components having the same size and configuration at low cost, handling the graphene conjugate in the manufacture of circuit components becomes a major issue. Furthermore, the pattern of the insulating layer formed on the surface of the graphene conjugate and the pattern of the conductive layer formed on the surface of the insulating layer become more difficult to accurately pattern the insulating layer and the conductive layer as the area of the graphene conjugate as a circuit board becomes smaller and the width of the rectangular circuit board becomes narrower. In the prior application, a graphene conjugated body serving as a circuit board is formed on the bottom surface of a container, and the graphene conjugated body is peeled off from the bottom surface of the container. Thereafter, in order to form an insulating layer on the surface of the graphene conjugated body, an insulating paste is applied to the surface of the graphene conjugated body, the graphene conjugated body is placed in a heat treatment device, and after the insulating paste is heat-treated, the graphene conjugated body is removed from the heat treatment device. Furthermore, in order to form a conductive layer on the graphene conjugated body, a conductive paste is applied to the surface of the insulating layer, the graphene conjugated body is placed in a heat treatment device, and after the conductive paste is heat-treated, the graphene conjugated body is removed from the heat treatment device. For this reason, the smaller the area and the narrower the width of the elongated graphene conjugated body, the more difficult it becomes to handle the graphene conjugated body. In the prior application, an insulating paste is applied to a surface of the graphene conjugate, the graphene conjugate is heat-treated, and an insulating layer is formed on the surface of the graphene conjugate. A conductive paste is applied to the surface of the insulating layer formed on the surface of the graphene conjugate, and the graphene conjugate is heat-treated, and a conductive layer is formed on the surface of the insulating layer. Therefore, the smaller the area of the graphene conjugate as a circuit board and the narrower the width of the rectangular graphene conjugate, the more difficult it becomes to accurately pattern the insulating layer and the conductive layer.
[0012] In contrast, in the present invention, firstly, an insulating layer made of a collection of insulating metal oxide particles is prepared separately from the graphene conjugate serving as a circuit board, and the prepared insulating layer is frictionally welded to the graphene conjugate. Meanwhile, in the prior application, an insulating paste is applied to the surface of the graphene conjugate, the graphene conjugate is heat-treated, and an insulating layer is formed on the surface of the graphene conjugate. Secondly, a conductive layer made of a collection of conductive metal particles is prepared separately from the graphene conjugate serving as a circuit board, and the prepared conductive layer is frictionally welded to the insulating layer. Meanwhile, in the prior application, a conductive paste is applied to the surface of the insulating layer formed on the graphene conjugate, the graphene conjugate is heat-treated, and a conductive layer is formed on the surface of the insulating layer. That is, in the present invention, the manufacture of the graphene conjugate as a circuit board, the formation of an insulating layer consisting of an assembly of insulating metal oxide particles bonded to each other, and the formation of a conductive layer consisting of an assembly of metal particles bonded by metallic bonds are separated, and each is manufactured or formed separately. Furthermore, an insulating layer is frictionally welded to a predetermined position on the surface of the graphene conjugate formed on the bottom surface of the container, and a conductive layer is frictionally welded to a predetermined position on the surface of the insulating layer. Therefore, the graphene conjugate is handled only once, which is the minimum necessary, only after the circuit component in which the insulating layer and the conductive layer are formed on the graphene conjugate is peeled off from the bottom of the container. In addition, the insulating layer and the conductive layer in the present invention are formed on the bottom surface of the container in the shape of the bottom surface, so that the insulating layer and the conductive layer can be formed on the bottom surface of the container even if the size and width of the insulating layer and the conductive layer are small. [Means for solving the problem]
[0013] A method for producing a circuit component in which a graphene joint obtained by friction welding graphene particles together is used as a circuit board, an insulating layer made of an assembly of fine particles of insulating metal oxide in which fine particles of the metal oxide are friction-welded to a surface of the circuit board, and a conductive layer made of an assembly of fine metal particles in which fine metal particles are metallically bonded to each other is friction-welded to the surface of the insulating layer, comprises the steps of: A collection of flake graphite particles or a collection of lump graphite particles is spread evenly on the surface of one of two parallel plate electrodes, the one parallel plate electrode is immersed in 1-butanol filled in a first container, the other parallel plate electrode is placed on top of the one parallel plate electrode, the two parallel plate electrodes are separated by the collection of flake graphite particles or the collection of lump graphite particles, and the two separated parallel plate electrodes are immersed in the 1-butanol, and then a direct current potential difference of a predetermined magnitude is applied to the gap between the two parallel plate electrodes, whereby an electric field equivalent to the value obtained by dividing the magnitude of the potential difference by the size of the gap between the two parallel plate electrodes is generated between the collection of flake graphite particles or the lump graphite particles. a first process of producing graphene aggregates in a container from a collection of graphite particles, the first process comprising: applying a voltage to a collection of graphite particles having a shape similar to that of the first container; simultaneously destroying all interlayer bonds of the basal planes forming the flake-like graphite particles or the lump-like graphite particles; and precipitating graphene aggregates corresponding to the basal planes in the gap between the two parallel plate electrodes; thereafter, expanding the gap between the two parallel plate electrodes; tilting the two parallel plate electrodes in the 1-butanol; applying vibration acceleration in three directions, left-right, front-back, and up-down, to the first container to move the graphene aggregates from the gap between the two parallel plate electrodes into the 1-butanol and dispersing the graphene aggregates in the 1-butanol; and removing the two parallel plate electrodes from the first container; A predetermined amount of the graphene aggregates dispersed in the 1-butanol is poured from the first container into a second container having a bottom shape corresponding to a shape of a circuit board, and a vibration acceleration in three directions, i.e., front-back, left-right, and up-down, is repeatedly applied to the second container as a vibration acceleration greater than the vibration acceleration applied in the first step, so that the graphene aggregates are aligned in a planar shape in the 1-butanol, and the graphene aggregates aligned in a planar shape are stacked one on top of the other via the 1-butanol to form the graphene aggregates in the second container; and further, the temperature of the second container is raised to the boiling point of the 1-butanol to extract the 1-butanol from the graphene aggregates. a second step of forming a graphene conjugate having the shape of the bottom surface of the container as a circuit board on a bottom surface of the container, the second step being a process of removing the plate from the second container; and a second step of forming a graphene conjugate having the shape of the bottom surface of the container as a circuit board on a bottom surface of the container, the second step being a process of removing the plate from the second container; a first metal compound having both a first property of precipitating a metal oxide by thermal decomposition in an air atmosphere and a second property of dispersing in methanol is dispersed in methanol to prepare a methanol dispersion, a predetermined amount of the methanol dispersion of the first metal compound is poured into a third container having a bottom shape that is the same as the shape of an insulating layer, the third container is then heated to the boiling point of methanol to precipitate a cluster of fine crystals of the first metal compound from the methanol dispersion of the first metal compound, the third container is then covered with a plate material that covers the entire surface of the cluster of fine crystals of the first metal compound, and the entire surface of the plate material is uniformly compressed with a compressive force smaller than that applied to the plate material in the second step to crush the cluster of fine crystals of the first metal compound and prepare a cluster of crystals finer than the fine crystals, a third step of forming an insulating layer on the bottom surface of the third container in the shape of the bottom surface of the container, the third step being performed by repeatedly applying vertical impact acceleration to the bottom surface of the third container to peel off the insulating layer from the bottom surface of the third container; the third step of forming an insulating layer on the bottom surface of the container in the shape of the bottom surface of the container, the third step being performed by repeatedly applying vertical impact acceleration to the bottom surface of the third container to peel off the insulating layer from the bottom surface of the third container; A second metal compound having both a first property of precipitating a metal by thermal decomposition in an air atmosphere and a second property of dispersing in methanol is dispersed in methanol to prepare a methanol dispersion, a predetermined amount of the methanol dispersion of the second metal compound is poured into a fourth container having a bottom shape that corresponds to the shape of the conductive layer, the fourth container is then heated to the boiling point of methanol to precipitate a collection of fine crystals of the second metal compound from the methanol dispersion of the second metal compound, and the fourth container is further heated to a temperature at which the second metal compound is thermally decomposed, thereby producing a metal. a fourth step of forming a conductive layer consisting of a collection of metal particles bonded together by metallic bonding on the bottom surface of the fourth container in the shape of the bottom surface of the container, the conductive layer consisting of a collection of metal particles bonded together by metallic bonding being formed on the bottom surface of the fourth container in the shape of the bottom surface of the container, the fourth step being a process of repeatedly applying to the bottom surface of the fourth container an impact acceleration in the vertical direction that is smaller than the impact acceleration applied to the bottom surface of the third container, and peeling off the conductive layer from the bottom surface of the fourth container; The insulating layer formed in the third step is superimposed on a predetermined position of the circuit board formed in the second step, a plate material is placed over the insulating layer to cover the entire surface of the insulating layer, and the entire surface of the plate material is evenly compressed with a compressive force smaller than the compressive force applied when bonding the metal oxide fine particles to each other by frictional heat in the third step, and the contact portion between the circuit board and the insulating layer is frictionally welded to bond the insulating layer to the circuit board. Thereafter, the plate material is removed from the insulating layer, and the conductive layer formed in the fourth step is superimposed on a predetermined position of the insulating layer, a new plate material is placed over the insulating layer to cover the entire surface of the conductive layer, and the insulating layer is frictionally welded to the circuit board. a fifth step of manufacturing a circuit component in which an insulating layer and a conductive layer are frictionally welded to a circuit board, the fifth step comprising a process of uniformly compressing the entire surface of the new plate material with a compressive force smaller than the compressive force applied when the new plate material was brought into contact with the insulating layer, frictionally welding the contact portions between the conductive layer and the insulating layer, and bonding the conductive layer to the insulating layer, after which the new plate material is removed from the conductive layer, and repeatedly applying vertical impact accelerations greater than the impact acceleration applied to the bottom surface of the third container to the bottom surface of the second container on which the circuit board is formed, thereby peeling off the circuit component in which the insulating layer and the conductive layer are bonded to the circuit board, from the bottom surface of the second container; The method for continuously carrying out the treatment consisting of the five steps includes using a graphene joint formed by friction welding graphene particles together as a circuit board, friction-welding an insulating layer made of an assembly of fine particles of insulating metal oxide formed by friction-welding fine particles of the metal oxide together onto a surface of the circuit board, and further friction-welding a conductive layer made of an assembly of fine particles of metal oxide formed by metallic bonding of fine particles of the metal oxide together onto the surface of the insulating layer, to produce a circuit component in which the insulating layer and the conductive layer are friction-welded onto the surface of the circuit board.
[0014] The treatment in each of the five steps of the present invention will be described. In the first step, a graphene cluster is produced from a cluster of graphite particles in 1-butanol. That is, a cluster of scaly graphite particles or a cluster of lump graphite particles packed in the gap between two parallel plate electrode pairs is immersed in 1-butanol, which is an insulator, and a direct current potential difference is applied to the two parallel plate electrode pairs. As a result, an electric field equivalent to the potential difference divided by the size of the gap between the two parallel plate electrode pairs is generated in the electrode gap in which the cluster of scaly graphite particles or the cluster of lump graphite particles is present. This electric field simultaneously applies a Coulomb force sufficient to destroy the interlayer bonds of the basal plane of the graphite crystal to all the pi electrons that are carriers of the interlayer bonds of the basal plane for all of the graphite particles. As a result, the pi electrons are released from the constraints on the pi orbitals, and all the pi electrons leave the pi orbitals and become free electrons. In other words, when the Coulomb force acting on the π electrons is given to the π electrons as a force greater than the interaction of the π orbitals, the π electrons are released from the constraints of the π orbitals and become free electrons. As a result, all of the π electrons that are responsible for the interlayer bonds of the basal planes no longer exist on the π orbitals, and all of the interlayer bonds of the basal planes made of graphite crystals that form the graphite particles are simultaneously destroyed for all of the graphite particles. As a result, a collection of basal planes made of graphite crystals, that is, a collection of graphene, is instantly produced in the gap between the two parallel plate electrode pairs. Since the two parallel plate electrode pairs are immersed in 1-butanol, the collection of graphene precipitated in the gap between the parallel plate electrode pairs does not scatter. The electrical conductivity of 1-butanol is 9.12×10 -7 It is an insulator with a dielectric constant of 17.5, and a dielectric constant of 1 S / m. Therefore, when a potential difference is applied between two parallel plate electrodes immersed in 1-butanol, an electric field is generated in the gap between the two parallel plate electrodes. Next, the graphene cluster is moved from the gap between the two parallel flat electrodes into 1-butanol. To this end, the gap between the two parallel flat electrodes is expanded in 1-butanol and then tilted in 1-butanol. After this, vibration acceleration in three directions is applied to the container into which 1-butanol has been poured, with each vibration acceleration applied for five seconds. This causes the graphene cluster to move from the gap between the two parallel flat electrodes into 1-butanol. After this, the two parallel flat electrodes are removed from the container. The magnitude of the vibration acceleration applied to the container is 0.2-0.3G depending on the size of the container. In the second step, a predetermined amount of the graphene aggregate dispersed in 1-butanol is poured from the first container into a second container having a bottom shape of a circuit board. That is, since the circuit boards are of various sizes and shapes, a container for forming a circuit board on the bottom of the container was used as the second container different from the first container. Next, vibration acceleration in three directions, front-back, left-right, and up-down, is applied to the second container three times for 5 seconds each. At this time, the graphene aggregates dispersed in 1-butanol are arranged in a planar shape in the 1-butanol, and the planar graphene aggregates are stacked and laminated through the 1-butanol to form the graphene aggregates in the second container. The magnitude of the vibration acceleration is set to a vibration acceleration of 0.3-0.5 G depending on the size of the second container, which is greater than the vibration acceleration applied to the first container in the first step. That is, in the second container, all the graphene is covered with low-viscosity, low-density 1-butanol and dispersed in the 1-butanol. When the vibration acceleration in three directions is applied to the second container three times for 5 seconds each, the low-viscosity, low-density 1-butanol moves in the direction of the vibration acceleration along with the graphene, which has almost no mass. On the other hand, the aspect ratio of graphene is the ratio of the long axis to the thickness, which is 3×10 3 -9×10 6is extremely large. Therefore, the graphene moves with the 1-butanol with the face up in the direction of the vibration acceleration. The graphene continues to rearrange in the 1-butanol with the face up. This causes the graphene aggregates to align in a planar shape in the 1-butanol, and the graphene aligned in a planar shape overlaps and stacks with the 1-butanol between them, a phenomenon that progresses in the 1-butanol. As a result, the graphene aggregates are formed in the second container, in which the graphene aligned in a planar shape in the 1-butanol and the graphene aligned in a planar shape overlap and stack with the 1-butanol between them. Furthermore, the second container is heated to the boiling point of 1-butanol, and 1-butanol is vaporized from the graphene aggregates. When 1-butanol vaporizes, moisture attached to the surface of the flake graphite particles or the lump graphite particles when refining the graphite particle aggregates from the graphite crystals vaporizes together with 1-butanol. As a result, the graphene is purified, and the purified graphene overlaps with each other. Thereafter, a plate material that covers the entire graphene aggregate is placed on the plate material, and the entire surface of the plate material is uniformly compressed. As a result, the purified graphene aggregates are stacked in a planar arrangement, overlapping each other, and the graphene is friction-welded with each other at the overlapping surfaces, and a graphene joint with high bonding strength is formed on the bottom surface of the second container in the shape of the bottom surface. The third step is a step of forming an insulating layer made of an assembly of insulating metal oxide particles bonded to each other. First, a first metal compound having both a first property of precipitating a metal oxide by thermal decomposition and a second property of dispersing in methanol is dispersed in methanol to prepare a methanol dispersion. That is, when methanol is evaporated from a methanol dispersion of the first metal compound, a collection of fine crystals of the first metal compound is precipitated as a collection of fine particles smaller than 100 nm. In contrast, when the first metal compound is dissolved in methanol, the metal constituting the first metal compound becomes a metal ion and is eluted in the methanol, and the dissolved first metal compound cannot be returned to the first metal compound before dissolution. Therefore, when methanol is evaporated from a methanol solution of the first metal compound, the first metal compound before dissolution does not precipitate. For this reason, a first metal compound that does not dissolve in methanol and disperses in methanol is used as the first metal compound that precipitates a metal oxide by thermal decomposition. Next, a predetermined amount of the methanol dispersion of the first metal compound is poured into a third container having the shape of the insulating layer as the bottom shape of the container. That is, the size and thickness of the insulating layer are determined in advance, and the size of the third container is determined based on this. After this, the methanol dispersion of the first metal compound required to form an insulating layer having the predetermined size and thickness is determined. Based on the results of this investigation, a required amount of the methanol dispersion of the first metal compound is poured into the third container. Furthermore, the third container is heated to the boiling point of methanol, and a collection of fine crystals of the first metal compound is precipitated from the methanol dispersion of the first metal compound. At this time, the collection of fine crystals of the first metal compound is precipitated as a collection of fine particles smaller than 100 nm. Since the first metal compound dispersed in a molecular state is precipitated as fine crystals, the fine crystals are a collection of crystals in which crystals forming single molecules of the first metal compound are accumulated. Therefore, when stress is applied to the fine crystals, the fine crystals are easily crushed. However, the finer the fine crystals are, the more difficult it is to apply stress to them, and there is a limit to how fine the fine crystals can be. After this, the third container is covered with a plate material that covers the entire collection of the microcrystals of the first metal compound, and the entire surface of the plate material is compressed evenly to crush the collection of the microcrystals of the first metal compound into a collection of crystals that are even finer than the microcrystals. At this time, since the relatively larger the size of the microcrystals, the easier they are to crush, the relatively larger microcrystals are crushed first, and the crushing of the microcrystals progresses while the compressive stress is applied. On the other hand, when the microcrystals are crushed, new voids are formed in the collection of microcrystals, and the collection of crushed and finer crystals moves into the voids and fills them. As the crushing of the microcrystals progresses, the crushed and finer crystals overlap at a high density, and the collection of finer crystals accumulates at a high density. When the crushing of the crystals reaches a limit size, the crushing of the microcrystals does not progress even if a compressive stress is applied to the plate material, and the plate material to which the compressive stress is applied no longer moves, and the repulsive force from the plate material increases. At this point, the process of compressing the surface of the plate material is stopped. As a result, the size of the fine crystals is reduced to approximately 20 nm, nearly one-fifth of the size at the time of precipitation. Furthermore, the third container is heated to a temperature at which the first metal compound is thermally decomposed, and a collection of metal oxide fine particles is precipitated. First, if foreign matter consisting of moisture or a compound having a hydroxyl group is adsorbed on the fine crystals, these foreign matter will vaporize preferentially. Next, the thermal decomposition of the fine crystals of the first metal compound begins, the first metal compound is thermally decomposed into organic molecules and metal oxide molecules, and when the vaporization of the organic molecules is completed, the metal oxide molecules gather to form granular metal oxide nanoparticles having a size of about 10 nm, and the nanoparticles precipitate all at once. At this time, the granular nanoparticles are precipitated by overlapping each other, the nanoparticles come into contact with each other and are stacked, and the collection of nanoparticles forms an insulating layer having a certain thickness depending on the amount of the methanol dispersion of the first metal compound injected into the third container. The metal oxide nanoparticles do not contain any impurities and precipitate as genuine metal oxide nanoparticles. After this, a compressive force larger than the compressive force when the collection of microcrystals of the first metal compound is crushed is evenly applied to the entire surface of the plate material, and the metal oxide fine particles having a size of about 10 nm are bonded together by frictional heat. That is, as described above, when the microcrystals are crushed into finer crystals, the collection of crystals having a size of about 20 nm is accumulated in a high density overlapping manner. After this, when the crystals having a size of about 20 nm are thermally decomposed, the collection of metal oxide nanoparticles having a size of about 10 nm is precipitated all at once in an overlapping manner, and the collection of nanoparticles overlaps and contacts each other. When such a collection of metal oxide nanoparticles is compressed, the nanoparticles first move very slightly, and the accumulation density in the collection of nanoparticles is further increased, and then, when it becomes difficult to move the nanoparticles, a compressive stress is applied to the nanoparticles. At this time, since the nanoparticles are refined to the limit size, the nanoparticles are not crushed, and excessive frictional heat is generated for a short time at the site where the nanoparticles contact each other, and the nanoparticles are frictionally welded at the contact area. In addition, the nanoparticles are frictionally welded to the bottom surface of the third container. As a result, an insulating layer made of a collection of metal oxide nanoparticles is formed on the bottom surface of the third container in the shape of the bottom surface. Since the metal oxide nanoparticles, which have been reduced to a minimum size, are frictionally welded together at the contact points, the insulating layer made of a collection of metal oxide nanoparticles has a certain mechanical strength and is not easily broken or deformed. In addition, it is not easily deformed by compressive stress. After this, an impact acceleration of 0.3-0.5G depending on the size of the container is applied intermittently to the bottom surface of the third container for 5 seconds, and the insulating layer formed on the bottom surface is peeled off from the bottom surface. The insulating layer, which is made of a collection of metal oxide nanoparticles, is also subjected to the impact force repeatedly for a short period of time. However, since the surface of the insulating layer opposite to the bottom surface of the third container is open to the atmosphere and not restrained, no compressive stress due to the impact force is generated in the insulating layer. In addition, since the nanoparticles of the insulating layer have already been frictionally welded together by the compressive force, the insulating layer is not destroyed or deformed by the impact force. The fourth step is to form a conductive layer made of a collection of metal particles bonded together by metallic bonds. First, a second metal compound having both a first property of precipitating a metal by thermal decomposition in an air atmosphere and a second property of dispersing in methanol is dispersed in methanol to prepare a methanol dispersion. That is, similar to the first metal compound precipitating a metal oxide by thermal decomposition described above, when methanol is evaporated from a methanol dispersion of the second metal compound, a collection of fine crystals of the second metal compound is precipitated as a collection of fine particles smaller than 100 nm. In contrast, when the second metal compound is dissolved in methanol, the metal constituting the second metal compound becomes a metal ion and is dissolved in methanol, and the dissolved second metal compound cannot be returned to the second metal compound before dissolution. Therefore, when methanol is evaporated from a methanol solution of the second metal compound, the second metal compound before dissolution does not precipitate. For this reason, a second metal compound that does not dissolve in methanol and disperses in methanol is used as the second metal compound that precipitates a metal by thermal decomposition. Next, a predetermined amount of the methanol dispersion of the second metal compound is poured into a fourth container having the shape of the conductive layer as the bottom shape of the container. That is, the size and thickness of the conductive layer are determined in advance, and the size of the fourth container is determined based on this. After this, the amount of the methanol dispersion of the second metal compound required to form a conductive layer having the predetermined size and thickness is determined. Based on the results of this investigation, the required amount of the methanol dispersion of the second metal compound is poured into the fourth container. Thereafter, the temperature of the fourth vessel is raised to the boiling point of methanol, and a cluster of microcrystals of the second metal compound is precipitated from the methanol dispersion of the second metal compound. As in the case of the first metal compound that precipitates a metal oxide by thermal decomposition described above, when the methanol is evaporated from the methanol dispersion of the second metal compound, a cluster of microcrystals of the second metal compound is precipitated as a cluster of fine particles smaller than 100 nm. Furthermore, the fourth container is heated to a temperature at which the second metal compound is thermally decomposed. First, if foreign matter consisting of moisture or a compound having a hydroxyl group is adsorbed to the fine crystals, these foreign matter will vaporize preferentially. Next, the thermal decomposition of the fine crystals of the second metal compound begins, and the second metal compound is thermally decomposed into organic molecules and metal molecules. When the vaporization of the organic molecules is completed, the metal molecules gather to form granular metal nanoparticles having a size of about 40-60 nm, and the collection of nanoparticles precipitates simultaneously at a high density. At this time, the metal nanoparticles do not contain any impurities and precipitate in an active state as genuine metal nanoparticles, so that the metal nanoparticles are metallically bonded to each other at the contact sites, and the collection of metal nanoparticles bonded by metallic bonds is formed as a conductive layer on the bottom surface of the fourth container. After this, the bottom surface of the fourth container is repeatedly subjected to impact acceleration in the vertical direction, and the conductive layer is peeled off from the bottom surface of the fourth container. Note that the conductive layer, which is a collection of metal nanoparticles, is also subjected to impact forces repeatedly for a short period of time, but since the surface of the conductive layer opposite to the bottom surface of the fourth container is open to the atmosphere and is not constrained, no compressive stress due to the impact force is generated in the conductive layer. In addition, since the metal nanoparticles of the conductive layer are already bonded to each other by metallic bonds, the conductive layer is not destroyed or deformed by the impact force. The fifth step is a step of frictionally bonding an insulating layer to the surface of the graphene conjugate as a circuit board, and further frictionally bonding a conductive layer to the surface of the insulating layer. First, the insulating layer formed in the third step is superimposed on a predetermined position of the graphene conjugate frictionally welded to the bottom surface of the second container in the second step, a plate material covering the entire insulating layer is placed on top of the graphene conjugate, and the entire surface of the plate material is evenly compressed to frictionally weld the contact portion between the graphene conjugate and the insulating layer. That is, the graphene conjugate is formed by frictionally welding graphene particles each having a thickness of 0.332 nm by overlapping each other. The surface of the graphene conjugate is close to a perfect flat surface. On the other hand, the insulating layer is a collection of nanoparticles in which nanoparticles of metal oxide having a size of about 10 nm are frictionally welded together at the contact portion. Therefore, when the insulating layer is superimposed on a predetermined position of the graphene conjugate and the entire insulating layer is evenly compressed, excessive frictional heat is generated for a short time at the portion where the collection of nanoparticles forming the bottom layer of the insulating layer contacts the graphene conjugate, and the nanoparticles of metal oxide are frictionally welded to the graphene conjugate. On the other hand, the insulating layer is frictionally welded to the graphene conjugate with a compressive force smaller than the compressive force applied when the metal oxide nanoparticles are bonded to each other by frictional heat in the third step, and therefore, since the collection of metal oxide nanoparticles forming the insulating layer has already been frictionally welded at the contact portion with a larger compressive force, there is no change in the collection of metal oxide nanoparticles forming the insulating layer when the entire insulating layer is uniformly compressed onto the surface of the graphene conjugate. Next, the plate is removed from the insulating layer, and the conductive layer formed in the fourth step is placed on a predetermined position of the insulating layer, and a new plate covering the entire surface of the conductive layer is placed on top of the new plate, and the entire surface of the new plate is compressed evenly. Since the hardness of the metal is lower than that of the metal oxide, the metal-bonded metal nanoparticles are first slightly plastically deformed. Next, at the contact portion between the conductive layer and the insulating layer, the metal-bonded metal nanoparticles are slightly plastically deformed. Furthermore, at the portion where the slightly plastically deformed metal nanoparticles contact the metal oxide nanoparticles, excessive frictional heat is generated for a short time, and the metal nanoparticles are frictionally welded to the metal oxide nanoparticles. Note that when the metal nanoparticles are plastically deformed, since all the nanoparticles are metallically bonded to each other, the metallic bonds between the nanoparticles are not broken, and the metallically bonded nanoparticles are plastically deformed. In addition, the compressive stress applied to the new plate is smaller than the compressive stress applied to the plate when the insulating layer is frictionally welded to the graphene conjugate. The reason for this is that the hardness of metal oxides is higher than that of metals, so that friction welding of metal oxide nanoparticles requires a larger compressive stress than friction welding of metal nanoparticles, and therefore, when friction welding a conductive layer to an insulating layer, there is no change in the insulating layer, which is made of a collection of metal oxide nanoparticles. Thereafter, a new plate material is removed from the conductive layer, and an impact acceleration greater than the impact acceleration applied to the bottom surface of the third container is repeatedly applied as an impact acceleration in the up-down direction to the bottom surface of the opposite side of the second container on which the graphene conjugate is formed, and the circuit component in which the insulating layer and the conductive layer are joined to the graphene conjugate is peeled off from the bottom surface of the second container. At this time, the impact acceleration is repeatedly applied to the graphene conjugate frictionally welded to the bottom surface of the second container for a short period of time, but the circuit component in which the insulating layer and the conductive layer are joined to the graphene conjugate is in an unconstrained state because the surface opposite to the bottom surface of the second container is open to the atmosphere, so no compressive force is generated in the circuit component, and the circuit component is not destroyed or deformed. In other words, since the graphene conjugate is already frictionally welded by compressive stress, the graphene conjugate to which no compressive stress is applied is not destroyed or deformed by the impact acceleration. Similarly, since the insulating layer and the conductive layer have already been friction-welded by compressive stress, the insulating layer and the conductive layer are not destroyed or deformed by the impact acceleration. In the present invention, the circuit component is manufactured by frictionally welding the insulating layer formed in the third step to the surface of the graphene conjugate formed on the bottom surface of the second container, and then frictionally welding the conductive layer formed in the fourth step to the surface of the insulating layer. Therefore, the graphene conjugate as the circuit board is handled only once, which is the minimum necessary, only after the circuit component having the insulating layer and the conductive layer formed thereon is peeled off from the bottom of the container. Therefore, the graphene conjugate is handled only once.
[0015] Here, we will explain the phenomenon in which, in the first step, an electric field applied to the gap between two parallel plate electrode pairs simultaneously destroys all of the interlayer bonds of the basal plane of the graphite crystals that form the graphite particles in the graphite particles packed in the gap between the two parallel plate electrode pairs. The carbon atoms forming the basal plane of the graphite crystals in the graphite particles have four valence electrons. Three of these valence electrons are σ electrons that form the basal plane of the graphite crystals, i.e., graphene. These σ electrons are covalently bonded to the σ electrons of three adjacent carbon atoms on the basal plane at an angle of 120 degrees to each other, forming a two-dimensional strong hexagonal network structure. The remaining valence electron is a π electron, which exists on a π orbital extending in a direction perpendicular to the basal plane. This π electron is weakly bonded to the π electrons of adjacent carbon atoms in the vertical direction perpendicular to the basal plane, and the basal planes are stacked in layers based on this weak bond. In other words, the basal planes, i.e., graphene, are bonded to each other in layers by the interaction of the π orbital, which is a weak bond. For this reason, graphite particles have the property of being easily peeled off at the basal plane of the graphite crystals, i.e., mechanical anisotropy. This mechanical anisotropy is known as the lubricity of graphite particles. When an electric field is applied to such graphite particles, a Coulomb force due to the electric field acts on all π electrons. When the Coulomb force acting on the π electrons acts on them with a force greater than the π orbital interaction acting on the π electrons, the π electrons are released from the constraints on the π orbitals. As a result, all π electrons leave the π orbitals and become free electrons. As a result, all π electrons that are responsible for the interlayer bonds on the basal plane of the graphite crystal are no longer on the π orbitals, and all interlayer bonds on the basal plane are simultaneously destroyed. In other words, when a π electron moves a distance of b between the layers of the graphite crystal due to the Coulomb force F, the π electron performs work W (W = b F). This work W is calculated as 35 millielectron volts (electron volts are a unit of energy that an electron possesses, and 1 electron volt is 1.62 × 10 -19When the electric field exceeds 100 joules, the π electrons are released from the constraints of the π orbital interactions and become free electrons. For example, if a pair of parallel flat electrodes is separated by a gap of 100 μm and a direct current potential difference of 10.6 kV or more is applied between the electrodes, all interlayer bonds of the basal planes of the graphite crystals are instantly destroyed. In this way, large amounts of graphene can be produced inexpensively by the extremely simple means of applying an electric field to a collection of inexpensive graphite particles. Furthermore, because all interlayer bonds of the basal planes are destroyed simultaneously, the resulting fine material is certainly a basal plane of graphite crystals, i.e., graphene. The term "graphite particle cluster" used here refers to a relatively small cluster of graphite particles, about 1 g to 100 g. In other words, flake graphite particles or lump graphite particles have a bulk density of 0.2-0.5 g / cm3. 3 It is a fine particle with a particle size distribution of 1-300 microns. Therefore, it is easy to pack a collection of graphite particles into the gap between two parallel plate electrode pairs, and it is also easy to apply a potential difference to the two parallel plate electrode pairs. When a potential difference is applied to the gap between the two parallel plate electrode pairs, an electric field is generated in all the areas where the graphite particles are packed. This electric field acts on the π electrons as a Coulomb force larger than the interaction of the π orbitals, and the π electrons are released from the constraints on the π orbitals and become free electrons. As a result, all interlayer bonds of the basal plane of the graphite crystals in the graphite particles are simultaneously destroyed, and a collection of basal planes of graphite crystals, that is, graphene, is produced in the gap between the two parallel plate electrode pairs. Here, we calculate the number of graphenes by assuming that all graphite particles consist of spheres with a diameter of 25 microns and that the true density of graphite is 2.25 × 10 3 kg / m 3 Therefore, the weight of one graphite particle is only 1.84 × 10 -8g. Also, assuming that the average thickness of a graphite particle is 10 microns, and the interlayer distance is 3.354 angstroms, a flake graphite particle with a thickness of 10 microns has 297,265 basal planes, i.e., stacked graphenes. Therefore, by destroying all the interlayer bonds of the basal planes made of graphite crystals, a collection of 297,265 graphenes can be obtained from just one spherical graphite particle. For this reason, when all the interlayer bonds of the basal planes are destroyed for a collection of spherical graphite particles weighing just 1 g, the total number of graphenes that can be obtained is 1.62 × 10 13 Therefore, an enormous number of graphene aggregates can be obtained from a small amount of graphite particle aggregate. The above-described method for producing graphene aggregates from graphite particle aggregates is described in Patent Document 3 by the present inventor.
[0016] Here, the functions and effects of the circuit board, insulating layer, and conductive layer manufactured or formed in each of the four steps described above will be described. In the first step, a collection of graphene particles was produced from the collection of graphite particles. Graphene is a material that combines the following six properties. First, it is a single crystal material made of a collection of carbon atoms that form a two-dimensional hexagonal network structure. It is an extremely lightweight material with a thickness of only 0.332 nm, which is equivalent to the size of a carbon atom, and has almost no mass. Second, it has a thermal conductivity of 1880 W / mK, which is 4.5 times that of silver, which has the highest thermal conductivity of all metals. Third, it has a volume resistivity of 1.3 μΩcm, which is even smaller than the volume resistivity of silver, which has the lowest volume resistivity of all metals, 1.6 μΩcm. Fourth, it is a single crystal material with a melting point of over 3000°C and a heat-resistant temperature of over 3000°C. Fifth, it is a tough material with a breaking strength of 42 N / m, which is more than 100 times that of steel, and a very large Young's modulus of 1020 GPa. Sixth, it is an extremely stable substance that does not react with acids or alkalis. In the second step, graphene is stacked on top of one another, and the stacked graphene is directly bonded by friction welding to produce a graphene conjugate. The graphene conjugate is composed only of graphene and has the six properties similar to those of graphene. Therefore, a circuit board made of the graphene conjugate is significantly superior to aluminum in all five properties of aluminum described in paragraph 9. This solves the first problem described in paragraph 9. Furthermore, the graphene conjugate is made by stacking graphene on top of each other and directly joining the overlapping graphene by friction welding. Therefore, the graphene conjugate is composed only of graphene and has properties similar to those of graphene. For example, even if 20 layers of graphene are stacked and joined, the thickness is only 6.6 nm. Therefore, the weight of the graphene conjugate is extremely small. Therefore, the weight of the circuit board is extremely small and it has almost no mass. Secondly, in the graphene composite, the thermal conductivity of the graphene composite is close to that of the graphene, because the heat is preferentially transferred in the direction of the graphene surface where the graphene is overlapped due to the anisotropy of the thermal conductivity of the graphene. In other words, the thermal conductivity of the graphene composite in the thickness direction is extremely small, and heat is preferentially transferred in the direction of the surface. Therefore, the graphene composite acts as a circuit board with better thermal conductivity than silver. Thirdly, the graphene conjugate exhibits electromagnetic wave shielding properties according to the volume resistivity of the graphene, and therefore functions as a circuit board with better electromagnetic wave shielding properties than silver. Fourth, because graphene has an extremely large aspect ratio (the ratio of area to thickness), and because the overlapping surfaces of the graphene are firmly bonded together, the mechanical strength of the graphene conjugate is close to that of graphene itself. Graphene has a high breaking strength of 42 N / m, which is more than 100 times stronger than steel, so it can function as a circuit board with extremely high breaking strength. Fifth, the heat resistance of the graphene joint, in which graphene is joined by friction welding, is close to that of graphene itself, and therefore it can act as a circuit board with heat resistance exceeding the melting point of metals. Sixth, the shape and area of the graphene conjugate can be freely changed according to the shape of the second container, so there is no restriction on the shape and size of the circuit board. Seventh, the graphene conjugate as a circuit board can be manufactured by a very simple process, and graphite particles are a very cheap industrial material, so that a cheap circuit board can be manufactured. In the third step, an insulating layer made of a collection of insulating metal oxide nanoparticles was formed. The nanoparticles are extremely small, about 10 nm, and therefore have an extremely large specific surface area. Therefore, the insulating resistance of the insulating metal oxide nanoparticles is significantly greater than the insulating resistance based on the volume resistivity of the metal oxide, compared to the insulating metal oxide bulk material. Furthermore, in an insulating layer made of a collection of nanoparticles, the resistance formed by the collection of nanoparticles stacked in the thickness direction is the resistance value of nanoparticles connected in series. In contrast, the resistance formed by the collection of nanoparticles connected in the surface direction is the resistance value of nanoparticles connected in parallel. Since the number of nanoparticles connected in the surface direction is overwhelmingly greater than the number of nanoparticles stacked in the thickness direction, the insulating layer made of a collection of nanoparticles has an increased insulation resistance as the insulating layer becomes thinner. Therefore, an insulating layer with a thinner insulating layer has a higher insulation resistance as the insulating layer becomes thinner, but it is easier to transfer heat to the circuit board. For example, if the thickness of the insulating layer is an insulating layer in which about 10 nanoparticles are stacked, the insulating layer will be thinner than 1 / 1000 of the thickness of the synthetic resin insulating layer described in paragraph 4. This forms an insulating layer that has significantly higher insulation resistance and significantly better thermal conductivity than conventional synthetic resin insulating layers. In addition, the melting point of insulating metal oxides is higher than that of metals, so that the insulating layer has better heat resistance than metals. Furthermore, the insulating layer is a collection of metal oxide nanoparticles that are frictionally welded together, and is an extremely thin film that is stacked to a thickness of, for example, about 100 nm, and further, the collection of metal oxide nanoparticles is frictionally welded to the circuit board and integrated with the circuit board. Furthermore, the surface of the insulating layer opposite to the circuit board is open to the atmosphere and is not restrained, so it is not subjected to stress from the circuit board, and even if mechanical stress and thermal stress are applied to the circuit board, the insulating layer will not peel off. On the other hand, the circuit board is a graphene joint in which graphenes that have extremely high mechanical strength and extremely excellent thermal conductivity are frictionally welded together. Therefore, even if any mechanical and thermal stress is applied to the circuit components, the circuit board is not damaged at all. Therefore, the insulating layer integrated with the circuit board is not damaged at all. This solves the second problem described in paragraph 9.Furthermore, since the size and shape of the insulating layer are determined by the shape of the third container, there are no restrictions on the size and shape of the insulating layer as long as the third container is 2-3 mm or larger, which can be processed. Furthermore, since the viscosity of the methanol dispersion of the first metal compound is close to that of methanol, the methanol dispersion of the first metal compound can be injected into a groove with a diameter of 2-3 mm. Furthermore, the first metal compound that precipitates a metal oxide by thermal decomposition is a general-purpose industrial chemical. Furthermore, the insulating layer is formed by a simple process in both cases. This solves the third problem described in paragraph 9. In the fourth step, a conductive layer consisting of a collection of conductive metal nanoparticles was formed. The thickness of the conductive layer needs to be increased depending on the magnitude of the current flowing through the conductive layer, but the thickness of the conductive layer can be freely changed depending on the amount of the methanol dispersion of the second metal compound injected into the fourth container. Furthermore, since the size and shape of the conductive layer are determined by the shape of the fourth container, there are no restrictions on the size and shape of the conductive layer as long as the fourth container is 2-3 mm or larger, which is a size that can be processed. Furthermore, since the viscosity of the methanol dispersion of the second metal compound is close to that of methanol, the methanol dispersion of the metal compound can be injected into a groove with a diameter of 2-3 mm. Furthermore, the second metal compound that precipitates a metal by thermal decomposition is a general-purpose industrial chemical. Furthermore, the conductive layer is formed by a simple process in both cases. This solves the third problem described in paragraph 9. As described above, the circuit board, insulating layer, and conductive layer of the present invention provide many advantageous effects.
[0017] The method for manufacturing a circuit component described in paragraph 13 is a method for simultaneously manufacturing a plurality of circuit components having the same configuration, and the method for simultaneously manufacturing a plurality of circuit components is as follows: A plurality of grooves having the same shape are formed in the second container described in the second step of paragraph 13, and the same amount of the graphene clusters dispersed in 1-butanol described in the first step of paragraph 13 is poured into each of the plurality of grooves, and vibration acceleration in three directions is repeatedly applied to the second container, so that the graphene clusters are aligned in a planar shape in the 1-butanol, and the graphene clusters aligned in a planar shape are stacked and laminated with the 1-butanol interposed therebetween to form the graphene clusters in each of the plurality of grooves, thereafter, the second container is heated to the boiling point of 1-butanol to evaporate the 1-butanol from the plurality of grooves, and the graphene clusters are stacked and overlapped with each other on the bottom surface of each of the plurality of grooves, and further, the plate material described in the second step of paragraph 13 has a plurality of protrusions having the same shape, a first step of simultaneously forming a plurality of graphene conjugates of the same shape on the bottom surface of each of the plurality of grooves in the shape of the bottom surface of the plurality of grooves, the first step being a step of preparing a plate material on which the plurality of protrusions are formed, overlapping the surface of the plate material on which the plurality of protrusions are formed with the surface of the second container on which the plurality of grooves are formed, and then evenly compressing the entire surface of the plate material on the opposite side on which the plurality of protrusions are formed, friction-welding the overlapping graphene formed on the bottom surfaces of the grooves, and forming a graphene conjugate consisting of an assembly of graphene joined by the friction welding on the bottom surface of each of the plurality of grooves in the shape of the bottom surface of the plurality of grooves as a circuit board, and then removing the plate material from the second container; A plurality of grooves having the same shape are formed in the third vessel described in the third step of paragraph 13, and the same amount of the methanol dispersion of the first metal compound described in the third step of paragraph 13 is poured into each of the plurality of grooves. Thereafter, the third vessel is heated to the boiling point of methanol, and the methanol is evaporated from each of the plurality of grooves, and a collection of fine crystals of the first metal compound is precipitated in each of the plurality of grooves. Furthermore, the plate material described in the third step of paragraph 13 has a plurality of protrusions having the same shape. a plate material having the plurality of protrusions, the side of the protrusions being in contact with the side of the groove, and the length of the protrusions being longer than the depth of the groove; the plate material having the plurality of protrusions is prepared, the surface of the plate material having the plurality of protrusions is placed on the surface of the third container having the plurality of grooves, and the plurality of protrusions are inserted into the plurality of grooves; thereafter, the entire surface of the plate material opposite to the surface on which the plurality of protrusions are formed is uniformly compressed with a compressive force smaller than the compressive force applied to the plate material in the first step, and the front surface of each of the plurality of grooves is compressed. The clusters of microcrystals of the first metal compound are crushed. Thereafter, the temperature of the third container is raised to a temperature at which the first metal compound is thermally decomposed, and clusters of insulating metal oxide nanoparticles are precipitated. Furthermore, a compressive force greater than the compressive force used when crushing the clusters of microcrystals of the first metal compound is evenly applied to the entire surface of the plate material, compressing the clusters of metal oxide nanoparticles precipitated in each of the plurality of grooves, and frictionally welding the contact portions between the metal oxide fine particles to form the nanoparticles in which the metal oxide fine particles are joined together. a second step of simultaneously forming a plurality of insulating layers of the same shape on the bottom surface of each of the plurality of grooves in the shape of the bottom surface, the second step being a process of simultaneously forming an insulating layer consisting of a collection of insulating particles on the bottom surface of each of the plurality of grooves in the shape of the bottom surface, removing the plate material from the third container, and then repeatedly applying impact acceleration in the vertical direction to a plurality of locations on the bottom surface of the third container corresponding to the portions of the third container where the plurality of grooves are formed, thereby simultaneously peeling off the insulating layer from the bottom surface of each of the plurality of grooves; A plurality of grooves of the same shape are formed in the fourth vessel described in the fourth step of paragraph 13, and the same amount of the methanol dispersion of the second metal compound described in the fourth step of paragraph 13 is poured into each of the plurality of grooves. Thereafter, the fourth vessel is heated to the boiling point of methanol to evaporate the methanol from the plurality of grooves, and a cluster of microcrystals of the second metal compound is precipitated in each of the plurality of grooves. Furthermore, the fourth vessel is heated to a temperature at which the second metal compound is thermally decomposed, whereby the cluster of fine metal particles in contact with each other is formed. a third step of simultaneously forming a plurality of conductive layers of the same shape on the bottom surface of each of the plurality of grooves, the conductive layers being precipitated all at once, the metal particles bonding with each other at the contact portions, and a collection of the metal particles bonding with each other at the contact portions, simultaneously forming a conductive layer on the bottom surface of each of the plurality of grooves; thereafter, a vertical impact acceleration smaller than the impact acceleration applied to the bottom surface of the third container is repeatedly applied to a plurality of locations on the bottom surface of the fourth container corresponding to the portions of the fourth container where the plurality of grooves are formed, thereby simultaneously peeling off the conductive layer from the bottom surface of each of the plurality of grooves; The insulating layer created in the second step is disposed at the same predetermined position on the surface of the graphene conjugate formed as the shape of the bottom surface of each of the plurality of grooves created in the first step; and the plate material described in the fifth step in paragraph 13 has a plurality of protrusions having the same shape, the shape of the tip of the protrusion has the shape of the insulating layer, the plurality of protrusions are formed at positions that contact the surfaces of the plurality of insulating layers arranged in the plurality of grooves, and have a length that compresses the plurality of insulating layers, and a plate material having the plurality of protrusions is prepared. the plate is placed on a second container in which the plurality of grooves are formed so that tips of the plurality of protrusions come into contact with the plurality of insulating layers, and the entire surface of the plate on the opposite side on which the plurality of protrusions are formed is uniformly compressed with a compressive force smaller than the compressive force applied when bonding metal oxide fine particles to each other by frictional heat in the second step, thereby frictionally bonding the contact portion between the graphene conjugate and the insulating layer, and bonding the insulating layer to the graphene conjugate; thereafter, the plate is removed from the second container; and further, the conductors created in the third step are attached to the same predetermined positions of each of the plurality of insulating layers. and a conductive layer is disposed on the new plate material described in the fifth step of paragraph 13, the new plate material having a plurality of protrusions of the same shape, the tip shape of the protrusions having the shape of the conductive layer, the plurality of protrusions being formed at positions contacting the surfaces of the plurality of conductive layers disposed in the plurality of grooves, and the plurality of protrusions having a length that compresses the plurality of conductive layers, a plate material having the plurality of protrusions is prepared, the plate material is superimposed on a second container in which the plurality of grooves are formed so that the plurality of protrusions contact the surfaces of the plurality of conductive layers, and the insulating layer is rubbed against the graphene conjugate. a second container that is formed on the second container and a second container that is formed on the second container; a second container that is formed on the second container and a third container that is formed on the second container; a second container that is formed on the second container and a third container that is formed on the second container; a second container that is formed on the second container and a third container that is formed on the second container;a fourth step of simultaneously manufacturing a plurality of circuit components in which an insulating layer and a conductive layer are bonded to the graphene conjugate, the fourth step including a process of simultaneously peeling the graphene conjugate off from the bottom surface of the second container; A method for simultaneously manufacturing a plurality of circuit components, in which the process consisting of the above four steps is carried out in succession, whereby a plurality of circuit components having the same configuration are simultaneously manufactured.
[0018] The process of each of the four steps of the present invention will be described below. In the first step, a container having a plurality of grooves of the same shape is prepared, as compared with the second container described in the second step in paragraph 13. That is, the purpose is to form a graphene conjugate having the same shape as a circuit board on the bottom surface of each of the plurality of grooves. Next, the same amount of graphene aggregate dispersed in 1-butanol described in the first step of paragraph 13 was poured into each of the grooves of the plurality of grooves. Furthermore, vibration acceleration in three directions is repeatedly applied to the second container for 5 seconds three times each. At this time, the graphene clusters dispersed in 1-butanol are arranged in a planar shape in the 1-butanol, and the planar graphene clusters are stacked and laminated by overlapping each other through the 1-butanol, forming a graphene cluster in each of the multiple grooves. The magnitude of the vibration acceleration is 0.3-0.5 G, which is greater than the vibration acceleration applied to the first container in the first step described in paragraph 13, depending on the size of the second container. In other words, when vibration acceleration in three directions is repeatedly applied to each of the multiple grooves, the low-viscosity, low-density 1-butanol moves in the direction of the vibration acceleration along with the graphene, which has almost no mass. On the other hand, when the aspect ratio of graphene is the ratio of the major axis to the thickness, the aspect ratio is 3×10 3 -9×10 6is extremely large. Therefore, the graphene moves with the surface facing up together with the 1-butanol in the direction of the vibration acceleration. The movement of the graphene rearranging in the 1-butanol with the surface facing up also continues. As a result, the graphene aggregates are aligned in a planar shape in the 1-butanol, and the graphene aligned in a planar shape overlap and stack with the 1-butanol interposed therebetween, and the graphene aggregates are formed in each of the multiple grooves. Furthermore, the temperature of the second container is raised to the boiling point of 1-butanol, and 1-butanol is vaporized from the plurality of grooves, and a collection of graphene in which the graphene overlaps with each other is formed on the bottom surface of each of the plurality of grooves. When the 1-butanol vaporizes, moisture attached to the surface of the flake graphite particles or the lump graphite particles during the purification of the collection of graphite particles from the graphite crystals is vaporized together with the 1-butanol. As a result, the graphene is purified, and the purified graphene overlaps with each other. Next, the plate material described in the second step of paragraph 13 is a plate material having a plurality of protrusions of the same shape, the side of the protrusions being shaped to contact the side of the groove, and the length of the protrusions being longer than the depth of the groove, and a plate material having a plurality of protrusions formed thereon is prepared. The surface of this plate having the plurality of protrusions is placed over the surface of the second container having the plurality of grooves, and the plurality of protrusions are inserted into the plurality of grooves. Then, the entire surface of the plate material opposite to the surface on which the multiple protrusions are formed is compressed evenly, whereby the purified graphene aggregates are stacked in a planar arrangement and overlapping manner, and the overlapping surfaces of the graphene are friction-welded to each other, forming a graphene joint with high joining strength on the bottom surface of the second container in the shape of the bottom surface. In the second step, first, a container is prepared in which a plurality of grooves having the same shape are formed, as compared with the third container described in the third step of paragraph 13. Each of the plurality of grooves has the shape of the insulating layer as the bottom shape of the groove. That is, the insulating layer is formed on the bottom surface of each of the plurality of grooves as the shape of the bottom surface. Furthermore, the same amount of the methanol dispersion of the first metal compound described in the third step of paragraph 13 is poured into each of the plurality of grooves. That is, the size and thickness of the insulating layer are determined in advance, and the size of the groove is determined based on this. After this, the methanol dispersion of the first metal compound required to form the insulating layer having the predetermined size and thickness is determined. Based on the result of this examination, the necessary amount of the methanol dispersion of the first metal compound is poured into each of the plurality of grooves. After this, the third container is heated to the boiling point of methanol, and methanol is vaporized from each of the grooves, and a collection of fine crystals of the first metal compound is precipitated in each of the grooves. At this time, the collection of fine crystals of the first metal compound is precipitated as a collection of fine particles smaller than 100 nm. Since the first metal compound that was dispersed in a molecular state is precipitated as fine crystals, the fine crystals are a collection of crystals in which crystals that form single molecules of the first metal compound are accumulated. For this reason, when stress is applied to the fine crystals, the fine crystals are easily crushed. However, the finer the fine crystals are, the more difficult it is to apply stress to them, and there is a limit to how fine the fine crystals can be. Furthermore, a plate material is prepared that has a plurality of protrusions of the same shape, the side surfaces of the protrusions are in contact with the side surfaces of the grooves, and the length of the protrusions is longer than the depth of the grooves, in relation to the plate material described in the third step of paragraph 13. The surface of the plate material that has the plurality of protrusions is superimposed on the surface of the third container that has the plurality of grooves, and the plurality of protrusions are inserted into the plurality of grooves. Furthermore, the entire surface of the plate material opposite to the surface on which the protrusions are formed is compressed uniformly with a compressive force smaller than that applied to the plate material in the first step, and the clusters of microcrystals of the first metal compound formed on the bottom surface of each of the grooves are crushed. At this time, since the relatively larger the size of the microcrystals, the easier they are to be crushed, the relatively larger microcrystals are crushed preferentially, and the crushing of the microcrystals progresses while the compressive stress is being applied. On the other hand, when the microcrystals are crushed, new voids are formed in the cluster of microcrystals, and the clusters of crushed and finer crystals move into the voids and fill them. As the crushing of the microcrystals progresses, the crushed and finer crystals overlap at a high density, and the clusters of finer crystals accumulate at a high density. When the crushing of the crystals reaches a limit size, the crushing of the microcrystals does not progress even if a compressive stress is applied to the plate material, and the plate material to which the compressive stress is applied no longer moves, and the repulsive force from the plate material increases. At this point, the process of compressing the surface of the plate material is stopped. As a result, the size of the fine crystals is reduced to approximately 20 nm, nearly one-fifth of the size at the time of precipitation. After this, the third container is heated to a temperature at which the first metal compound is thermally decomposed, and a collection of insulating metal oxide nanoparticles is precipitated. First, if foreign matter consisting of moisture or a compound having a hydroxyl group is adsorbed on the fine crystals, these foreign matter will vaporize preferentially. Next, the thermal decomposition of the fine crystals of the first metal compound begins, the first metal compound is thermally decomposed into organic molecules and metal oxide molecules, and when the vaporization of the organic molecules is completed, the metal oxide molecules gather to form granular metal oxide nanoparticles having a size of about 10 nm, and the nanoparticles precipitate all at once. At this time, the granular nanoparticles are precipitated by overlapping each other, the nanoparticles come into contact with each other and are stacked, and the collection of nanoparticles forms an insulating layer of a certain thickness depending on the amount of the methanol dispersion of the first metal compound injected into the third container. The metal oxide nanoparticles do not contain any impurities and precipitate as genuine metal oxide nanoparticles. Furthermore, a compressive force larger than the compressive force when the collection of microcrystals of the first metal compound is crushed is evenly applied to the entire surface of the plate material, the collection of nanoparticles of metal oxide precipitated in each of the grooves is compressed, the metal oxide fine particles are bonded to each other by frictional heat, and an insulating layer consisting of the collection of fine particles in which the metal oxide fine particles are bonded to each other is formed on the bottom surface of each of the grooves in the shape of the bottom surface. That is, when the microcrystals are crushed into finer crystals, a collection of crystals having a size of about 20 nm is overlapped and accumulated at a high density. After this, when the crystals having a size of about 20 nm are thermally decomposed, a collection of nanoparticles of metal oxide having a size of about 10 nm is precipitated all at once overlapping each other, and the collection of nanoparticles overlaps and contacts each other. When such a collection of nanoparticles of metal oxide is compressed, at first, the nanoparticles move very slightly, and the accumulation density in the collection of nanoparticles is further increased, and then, when it becomes difficult to move the nanoparticles, a compressive stress is applied to the nanoparticles. At this time, since the nanoparticles are miniaturized to the limit of size, the nanoparticles do not break down, and excessive frictional heat is generated for a short time at the site where the nanoparticles contact each other, and the nanoparticles are frictionally welded at the contact area. Also, the nanoparticles are frictionally welded to the bottom surface of the third container. As a result, an insulating layer made of a collection of metal oxide nanoparticles is formed on the bottom surface of each of the plurality of grooves in the shape of the bottom surface. After this, a vertical impact acceleration of 0.3-0.5G is repeatedly applied to a plurality of locations on the bottom surface of the third container corresponding to the portion where the plurality of grooves are formed, depending on the size of the container, and the insulating layer is simultaneously peeled off from the bottom surface of each of the plurality of grooves. The insulating layer, which is made of a collection of nanoparticles of metal oxide, is also subjected to the impact force repeatedly for a short period of time. However, the surface opposite to where the insulating layer contacts the bottom surface of the groove is open to the atmosphere and is not restrained, so no compressive stress due to the impact force is generated in the insulating layer. In addition, since the nanoparticles of the insulating layer have already been frictionally welded together by the compressive force, the insulating layer is not destroyed or deformed by the impact force. In the third step, a container is prepared in which a plurality of grooves of the same shape are formed, as compared with the fourth container described in the fourth step in paragraph 13. The shape of the bottom surface of the groove has the shape of the conductive layer. In other words, the size and thickness of the conductive layer are determined in advance, and the size of the groove is determined based on this. After this, the methanol dispersion of the second metal compound required to form a conductive layer of the predetermined size and thickness is identified. Based on the results of this investigation, the necessary amount of the methanol dispersion of the second metal compound is poured into each of the plurality of grooves in the same amount. Next, the fourth container is heated to the boiling point of methanol, and the methanol is vaporized from the multiple grooves, and a collection of microcrystals of the second metal compound is precipitated in each of the multiple grooves as a collection of fine particles smaller than 100 nm. Furthermore, the fourth container is heated to a temperature at which the second metal compound is thermally decomposed. If foreign matter consisting of moisture or a compound having a hydroxyl group is adsorbed on the microcrystals at first, these foreign matter are vaporized preferentially. Next, the thermal decomposition of the microcrystals of the second metal compound begins, and the second metal compound is thermally decomposed into organic molecules and metal molecules. When the vaporization of the organic molecules is completed, the metal molecules gather together to form granular metal nanoparticles having a size of about 40-60 nm, and the collection of nanoparticles is precipitated all at once at a high density. In this case, the metal nanoparticles do not contain any impurities and precipitate in an active state as true metal nanoparticles, so that the metal nanoparticles form metallic bonds at the contact sites, and a collection of metal nanoparticles joined by metallic bonds forms a conductive layer on the bottom surface of each of the multiple grooves. After this, a vertical impact acceleration smaller than the impact acceleration applied to the bottom surface of the third container is repeatedly applied to a plurality of locations on the bottom surface of the fourth container corresponding to the portion where the plurality of grooves of the fourth container are formed, and the conductive layer is simultaneously peeled off from the bottom surface of each of the plurality of grooves. Note that the conductive layer made of a collection of metal nanoparticles is also repeatedly subjected to impact forces for a short period of time, but since the surface opposite to where the conductive layer contacts the bottom surface of the groove is open to the atmosphere and not restrained, no compressive stress due to the impact force is generated in the conductive layer. In addition, since the conductive layer is already bonded between the metal nanoparticles by metallic bonds, the conductive layer is not destroyed or deformed by the impact force. In the fourth step, first, the insulating layer prepared in the second step is disposed at a predetermined position on the surface of the graphene conjugate formed on the bottom surface of each of the plurality of grooves prepared in the first step. Next, a plurality of protrusions having the same shape, the tip shape of the protrusions having the shape of the insulating layer, the plurality of protrusions being formed at positions where they contact the surfaces of the plurality of insulating layers and having a length that compresses the plurality of insulating layers, is formed on the plate material described in the fifth step of paragraph 13, to prepare the plate material. Furthermore, the plate is placed on a second container in which a plurality of grooves are formed so that the plurality of protrusions come into contact with the plurality of insulating layers, and the entire surface of the opposite side of the plate on which the plurality of protrusions are formed is evenly compressed with a compressive force smaller than the compressive force applied when the metal oxide fine particles are bonded together by frictional heat in the second step. That is, the graphene conjugate is formed by frictionally bonding graphene particles each having a thickness of 0.332 nm that are overlapped with each other, so that the surface of the graphene conjugate is close to a perfect flat surface. On the other hand, the insulating layer is a collection of nanoparticles in which metal oxide nanoparticles each having a size of about 10 nm are frictionally bonded together at the contact portion. Therefore, when the insulating layer is placed on a predetermined position of the graphene conjugate and the entire insulating layer is evenly compressed, excessive frictional heat is generated for a short time at the portion where the collection of nanoparticles forming the bottom layer of the insulating layer contacts the graphene conjugate, and the metal oxide nanoparticles are frictionally bonded to the graphene conjugate. On the other hand, since the insulating layer is frictionally welded to the graphene conjugate with a compressive force smaller than the compressive force applied when the metal oxide fine particles are bonded together by frictional heat in the third step described above, the metal oxide nanoparticles forming the insulating layer are already frictionally welded together at the contact portion with a larger compressive force, so that when the entire insulating layer is compressed evenly onto the surface of the graphene conjugate, there is no change in the collection of metal oxide nanoparticles forming the insulating layer.The plate material is then removed. Furthermore, the conductive layer created in the third step is disposed at a predetermined position of each of the plurality of insulating layers. Also, a new plate material described in the fifth step of paragraph 13 is provided with a plurality of protrusions having the same shape, the tip shape of the protrusions being the shape of the conductive layer, the plurality of protrusions being formed at positions where they contact the surfaces of the plurality of conductive layers disposed in the plurality of grooves, and the plurality of protrusions are characterized by having a length that compresses the plurality of conductive layers, and the plurality of protrusions are formed on the plate material to prepare the plate material. Thereafter, the plate material is placed on a second container in which a plurality of grooves are formed so that the plurality of protrusions come into contact with the surfaces of the plurality of conductive layers. The entire surface of the plate material opposite to the surface on which the plurality of protrusions are formed is uniformly compressed with a compressive force smaller than the compressive force applied when frictionally bonding the insulating layer to the graphene conjugate, thereby frictionally bonding the contact areas between the plurality of conductive layers and the plurality of insulating layers to bond the conductive layer to the insulating layer. Since the hardness of the metal is lower than that of the metal oxide, the metal-bonded nanoparticles are first plastically deformed slightly. Next, at the contact portion between the conductive layer and the insulating layer, the metal-bonded nanoparticles are plastically deformed slightly. Furthermore, excessive frictional heat is generated for a short time at the portion where the slightly plastically deformed metal nanoparticles contact the metal oxide nanoparticles, and the metal nanoparticles are frictionally welded to the metal oxide nanoparticles. When the metal nanoparticles are plastically deformed, all the nanoparticles are metallically bonded to each other, so the metallic bonds between the nanoparticles are not broken, and the metallically bonded nanoparticles are plastically deformed slightly. On the other hand, the compressive stress applied to the new plate material is smaller than the compressive stress applied to the plate material when the insulating layer is frictionally welded to the graphene conjugate. The reason for this is that the hardness of the metal oxide is higher than the hardness of the metal, so that when the metal oxide nanoparticles are frictionally welded to each other, a larger compressive stress is required when the metal nanoparticles are frictionally welded to each other. Therefore, when the conductive layer is frictionally welded to the insulating layer, there is no change in the insulating layer, which is made of a collection of nanoparticles of metal oxide. After this, the new plate material is removed from the conductive layer. Furthermore, a vertical impact acceleration greater than the impact acceleration applied to the bottom surface of the third container is repeatedly applied to a plurality of locations on the bottom surface of the second container corresponding to the locations where the plurality of grooves of the second container are formed, and a plurality of circuit components in which an insulating layer and a conductive layer are joined to the graphene conjugate are simultaneously peeled off from the bottom surface of the second container. At this time, the impact acceleration is repeatedly applied to the graphene conjugate frictionally welded to the bottom surface of the second container for a short period of time, but since the surface of the circuit components in which an insulating layer and a conductive layer are joined to the graphene conjugate is not constrained and is open to the atmosphere on the side opposite to the bottom surface of the second container, no compressive force is generated in the circuit components, and the circuit components are not destroyed or deformed. In other words, since the graphene conjugate is already frictionally welded by compressive stress between the graphene conjugates, the graphene conjugate to which no compressive stress is applied is not destroyed or deformed by the impact acceleration. Similarly, since the insulating layer and the conductive layer are already frictionally welded by compressive stress, the insulating layer and the conductive layer are not destroyed or deformed by the impact acceleration. As a result, multiple circuit components in which an insulating layer and a conductive layer are bonded to a graphene conjugate can be simultaneously manufactured, which makes it possible to manufacture separate circuit components at a lower cost than the method of manufacturing a single circuit component described in paragraph 13. In addition, in the manufacture of the circuit component in the present invention, an insulating layer is frictionally welded to the surface of the graphene conjugate formed on the bottom surface of the second container, and a conductive layer is frictionally welded to the surface of the insulating layer, similarly to the manufacture of the circuit component described in paragraph 13. Therefore, the graphene conjugate as the circuit board is handled only once, which is the minimum necessary, only after the circuit component having the insulating layer and the conductive layer formed thereon is peeled off from the bottom of the container. Therefore, the graphene conjugate is handled only once.
[0019] Here, the functions and effects of the circuit board, insulating layer, and conductive layer manufactured or formed in each of the three steps described above will be described. In the first step, graphene conjugates having the same shape and thickness are simultaneously produced by stacking graphene on the bottom surface of each of the grooves and directly bonding the stacked graphene on each other by friction welding. The graphene conjugate is made of only graphene and has the six properties described in paragraph 16. Therefore, a circuit board made of the graphene conjugate is significantly superior to aluminum in all of the five properties of aluminum described in paragraph 9. This solves the first problem described in paragraph 9. In addition, the method for producing the graphene conjugate is the same as the method described in paragraph 13, so the graphene conjugate has the seven properties described in paragraph 16. In the second step, an insulating layer consisting of an aggregate of insulating metal oxide nanoparticles is simultaneously formed on the bottom surface of each of the multiple grooves. Since the method for forming the insulating layer is the same as the method described in paragraph 13, the insulating layer has the various properties described in paragraph 16. This solves the second and third problems described in paragraph 9. In the third step, a conductive layer consisting of a collection of conductive metal nanoparticles is simultaneously formed on the bottom surface of each of the plurality of grooves. Since the method for forming the conductive layer is the same as the method described in paragraph 13, the conductive layer has the various properties described in paragraph 16. This solves the third problem described in paragraph 9.
[0020] The method for forming an insulating layer described in the third step of paragraph 13 includes the steps of: The first metal compound that precipitates a metal oxide upon thermal decomposition described in the third step of paragraph 13 is an aluminum carboxylate compound, such as aluminum caprylate, aluminum benzoate, or aluminum naphthenate, which precipitates aluminum oxide upon thermal decomposition, and the aluminum carboxylate compound is used as the first metal compound that precipitates aluminum oxide upon thermal decomposition, and a treatment method for forming an insulating layer consisting of a collection of insulating aluminum oxide particles friction-bonded together on the bottom surface of a third container in the shape of the bottom surface according to the treatment method described in the third step of paragraph 13 is the treatment method for forming an insulating layer described in the third step of paragraph 13.
[0021] That is, an aluminum carboxylate compound in which an aluminum ion is coordinated to a carboxylate ion, which is an anion generated by ionization of a carboxylic acid, precipitates insulating aluminum oxide by thermal decomposition in an air atmosphere. This aluminum carboxylate compound also disperses in methanol at a concentration of nearly 10% by weight. Therefore, in the third step described in paragraph 13, this aluminum carboxylate compound becomes a first metal compound that combines two properties. Therefore, the aluminum carboxylate compound becomes a raw material for forming an insulating layer consisting of a collection of aluminum oxide fine particles. Such aluminum carboxylate compounds include aluminum caprylate, aluminum benzoate, and aluminum naphthenate. Furthermore, aluminum carboxylate compounds are inexpensive industrial chemicals that can be easily synthesized. That is, when the commonly used carboxylic acids, caprylic acid, benzoic acid, or naphthenic acid, are reacted with a strong alkali, an alkali metal carboxylate compound made of these carboxylic acids is produced. Then, when the alkali metal carboxylate compound is reacted with an inorganic aluminum compound, an aluminum carboxylate compound is synthesized. That is, aluminum carboxylate compounds are aluminum compounds in which aluminum ions are coordinated to carboxylate ions, which are anions generated by ionization of carboxylic acid. That is, in aluminum carboxylate compounds, the carboxylate ions approach and coordinate to the aluminum ions, which are the largest ions, so that the distance between the aluminum ions and the oxygen ions that make up the carboxylate ions is short. This results in the longest distance between the ions that are covalently bonded to the oxygen ions on the opposite side of the aluminum ions. When the temperature of aluminum carboxylate compounds with such molecular structure exceeds the boiling point of the carboxylic acid, the bond between the oxygen ions and the ions that are covalently bonded to the aluminum ions on the opposite side of the aluminum ions is broken, and the aluminum ions and oxygen ions are decomposed into aluminum oxide, which is a compound of the aluminum ions and the oxygen ions, and the carboxylic acid. When the temperature is further increased, the carboxylic acid takes the heat of vaporization and vaporizes, and immediately after the vaporization of the carboxylic acid is completed, granular aluminum oxide particles with a size of 40-60 nm are precipitated. As a result, aluminum oxide is precipitated in the temperature range of 300-330°C in the atmosphere, depending on the boiling point of the carboxylic acid. Aluminum acetate is also an aluminum carboxylate compound in which an aluminum ion is coordinately bonded to a carboxylate ion, but it precipitates amorphous aluminum oxide by thermal decomposition. The composition of amorphous aluminum oxide is Al 2 O 3 The composition deviates from that of 14 Since the resistivity is significantly lower than Ωcm, it is not suitable as a raw material for forming an insulating layer. Incidentally, aluminum oxide is a material that is extremely hard with a Mohs hardness of 9 and a compressive strength of 2350 MPa, making it difficult to break. Therefore, even if excessive stress is applied to aluminum oxide fine particles having a size of about 10 nm when forming an insulating layer, the aluminum oxide fine particles will not be broken. That is, in the third step described in paragraph 13, when methanol is evaporated from a methanol dispersion of an aluminum carboxylate compound, a collection of fine crystals smaller than 100 nm of the aluminum carboxylate compound is precipitated. When this collection of fine crystals is crushed, a collection of crystals having a size of about 20 nm is accumulated in a high density, overlapping each other. After this, when the crystals having a size of about 20 nm are thermally decomposed, a collection of aluminum oxide nanoparticles having a size of about 10 nm is precipitated all at once, overlapping each other, and the collection of nanoparticles overlaps and contacts each other. When such a collection of aluminum oxide nanoparticles is compressed, the nanoparticles first move very slightly, further increasing the accumulation density in the collection of nanoparticles, and then, when it becomes difficult to move the nanoparticles, a compressive stress is applied to the nanoparticles. At this time, since the nanoparticles are miniaturized to the limit of size, the nanoparticles do not break down, and excessive frictional heat is generated for a short time at the site where the nanoparticles contact each other, and the nanoparticles are frictionally welded at the contact area. The nanoparticles are also frictionally welded to the bottom surface of the third container. As a result, an insulating layer consisting of a collection of aluminum oxide nanoparticles is formed on the bottom surface of the third container in the shape of the bottom surface. In other words, since aluminum oxide has a high heat resistance of 1500°C, the aluminum oxide fine particles are firmly bonded to each other at the contact area by frictional heat, and an insulating layer with a certain mechanical strength is formed. On the other hand, aluminum oxide has a volume resistivity of 10 14 It is an insulator with a resistance of Ωcm or more. Furthermore, the thickness of the insulating layer formed on the surface of the graphene junction is thin, at submicron levels, and the shape effect of the insulating layer makes the insulation resistance even greater. For example, if the insulating layer is 0.5 μm thick, 1 cm wide, and 10 cm long, the insulation resistance is 2 × 10 19Ω or more. In other words, by breaking down aluminum oxide into fine particles and bonding these fine particles together, an extremely thin insulating layer can be formed. The shape of this thin insulating layer significantly increases the insulation resistance. In addition, because the insulating layer is extremely thin, it has excellent thermal conductivity. Furthermore, the maximum operating temperature of aluminum oxide is high at 1500°C, and the withstand voltage of the insulating layer does not change at high temperatures. Furthermore, the thermal conductivity of aluminum oxide is 40 W / mK, which is high for an insulator. Incidentally, the thermal conductivity of epoxy resin, which is a conventional insulating layer, is 0.17-0.21 W / mK. Therefore, aluminum oxide has a thermal conductivity nearly 200 times that of epoxy resin. Furthermore, the insulating layer is thin, at submicron thickness, and insulating layers made of aluminum oxide have excellent thermal conductivity. As a result, although the insulating layer is an insulator with high insulation resistance, it transmits heat well to the graphene conjugate, and heat is released to the outside world from the graphene conjugate with a specified area, which has excellent thermal conductivity. The insulating layer made of the collection of aluminum oxide particles described above simultaneously solves the three problems that the synthetic resin insulating layer described in paragraph 4 has.
[0022] The process for forming the conductive layer described in the fourth step of paragraph 13 includes the steps of: The fourth step in paragraph 13 describes a treatment method in which the second metal compound that precipitates a metal upon thermal decomposition is any one of copper carboxylate compounds consisting of copper octylate, copper laurate, and copper stearate, which precipitate copper upon thermal decomposition, and the copper carboxylate compound is used as the metal compound that precipitates copper upon thermal decomposition, and a conductive layer consisting of a collection of copper fine particles in which conductive copper fine particles are metallically bonded to each other is formed on the bottom surface of a fourth container in the shape of the bottom surface according to the treatment method described in the fourth step in paragraph 13.
[0023] That is, a copper carboxylate compound having both the first feature that oxygen ions constituting a carboxyl group are covalently bonded to copper ions and the second feature that the compound is composed of a carboxylic acid made of a saturated fatty acid precipitates copper with excellent electrical and thermal conductivity by thermal decomposition in an air atmosphere. In addition, the copper carboxylate compound is dispersed in methanol at nearly 10% by weight. Therefore, in the fourth step described in paragraph 13, the copper carboxylate compound becomes a second metal compound having both properties. Therefore, the copper carboxylate compound becomes a raw material for copper fine particles that form a conductive layer. Examples of such copper carboxylate compounds include copper carboxylate compounds made of saturated fatty acids such as copper octylate, copper laurate, and copper stearate. Depending on the boiling points of these carboxylic acids, copper precipitates in the temperature range of 290-430°C in an air atmosphere. In addition, copper carboxylate compounds are inexpensive industrial chemicals that can be easily synthesized. That is, when a carboxylic acid, which is a general-purpose organic acid, is reacted with a strong alkali, an alkali metal carboxylate compound is produced. Then, when the alkali metal carboxylate compound is reacted with an inorganic copper compound, the copper carboxylate compound is synthesized. That is, the carboxylate copper compound having both of these characteristics is a copper compound in which copper ions are covalently bonded to carboxylate ions, which are anions generated by ionization of carboxylic acid. That is, in the carboxylate copper compound, the carboxylate ions approach and covalently bond to the copper ion, which is the largest ion, so that the distance between the oxygen ions constituting the carboxyl group and the copper ion is longer than the distance between the other ions. When the carboxylate copper compound having such molecular structure characteristics is heat-treated in an air atmosphere, the bond between the oxygen ions constituting the carboxyl group and the metal ions is broken at the boiling point of the carboxylic acid, and the carboxylic acid and the metal are separated. Furthermore, the carboxylic acid takes the heat of vaporization and vaporizes, and immediately after the vaporization of the carboxylic acid is completed, the granular copper particles having a size of 40-60 nm come into contact with each other and precipitate all at once. At this time, the copper nanoparticles do not contain any impurities and precipitate in an active state as genuine copper nanoparticles, so that the copper nanoparticles are metallically bonded to each other at the contact sites, and a collection of copper nanoparticles bonded by metallic bonds is formed as a conductive layer on the bottom surface of the fourth container. On the other hand, copper carboxylate compounds made from unsaturated fatty acids have an excess of carbon atoms relative to hydrogen atoms compared to copper carboxylate compounds made from saturated fatty acids, so copper oxide precipitates upon thermal decomposition. For example, copper oleate precipitates as copper oxide, Cu 2 O and copper oxide CuO are precipitated at the same time, and the cost of reducing them to copper is required. 2 O must first be oxidized to copper oxide (CuO) in an atmosphere that is richer in oxygen gas than the air, and then reduced to copper in a reducing atmosphere, which increases the cost of the reduction process. Copper is a soft metal with a Mohs hardness of 3.0. On the other hand, the Mohs hardness of aluminum oxide is high, at 9. Therefore, in the fifth step described in paragraph 13, when the conductive layer is frictionally welded to the insulating layer, compressive stress is applied to the copper particles having a size of 40-60 nm, and the copper particles are easily plastically deformed, and excessive frictional heat is concentrated and generated at the contact site where the plastically deformed copper particles come into contact with the aluminum oxide particles. Since the melting point of copper is high at 2562°C, the plastically deformed copper particles are bonded by frictional heat at the contact site with the aluminum oxide particles, and a conductive layer with a certain mechanical strength is bonded on the insulating layer. Note that when the copper particles are plastically deformed, all the copper particles are metallically bonded to each other, so the metallic bonds between the copper particles are not destroyed, and the metallically bonded copper particles are plastically deformed. Copper has a volume resistivity of 1.7 μΩcm and a thermal conductivity of 401 W / mK, making it the second most conductive and thermally conductive metal after silver. Therefore, when a large current flows through the conductive layer, or when components such as power devices and LEDs generate heat, the generated heat is efficiently transferred through the copper conductive layer to the aluminum oxide insulating layer, and then transferred from the insulating layer, which has excellent thermal conductivity, to the graphene conjugate, which also has excellent thermal conductivity, and finally released to the outside world from the graphene conjugate, which has a certain area. The conductive layer needs to be thickened according to the magnitude of the current flowing through it, but even if the conductive layer becomes thicker, the thermal conductivity of the conductive layer does not decrease because of the high thermal conductivity of copper. [Brief description of the drawings]
[0024] [Figure 1]FIG. 2 is an enlarged schematic diagram showing a part of a side surface of a graphene bonded body in which graphene particles are overlapped and bonded to each other. [Diagram 2] FIG. 2 is a front view of a first circuit component in which an insulating layer and a conductive layer are friction-welded to a surface of graphene of a circuit board. [Diagram 3] FIG. 13 is a front view of a container for simultaneously forming ten second circuit components in which an insulating layer and a conductive layer are friction-welded onto the graphene surface of a circuit board. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0025] EMBODIMENT 1 This embodiment relates to the aluminum carboxylate compound described in paragraphs 20-21. The aluminum carboxylate compound precipitates aluminum oxide by thermal decomposition and has the property of being dispersible in methanol without dissolving in methanol. It will be explained that aluminum benzoate, in which an oxygen ion constituting a carboxyl group of benzoic acid is coordinately bonded to an aluminum ion, is suitable as an aluminum compound that precipitates aluminum oxide. Substances that precipitate aluminum oxide by thermal decomposition must be liquefied to precipitate fine crystals of aluminum compounds. Inorganic aluminum compounds such as aluminum hydroxide, aluminum chloride, aluminum nitrate, and aluminum sulfate dissolve aluminum ions into the liquefied inorganic aluminum compounds, and many of the aluminum ions are unable to participate in the precipitation of aluminum oxide. Therefore, aluminum compounds must have the property of not dissolving in a solvent but dispersing in the solvent. Furthermore, if the aluminum compound can be dispersed in methanol, the most commonly used organic solvent, the aluminum compound will be uniformly dispersed in the solvent, and when the methanol is evaporated from the methanol dispersion of the aluminum compound, a collection of fine crystals of the aluminum compound will precipitate. Inorganic aluminum compounds do not disperse in methanol. For this reason, it is preferable that the aluminum compound that precipitates aluminum oxide by thermal decomposition is an organic aluminum compound rather than an inorganic aluminum compound. Furthermore, the organoaluminum compound must be thermally decomposed to precipitate aluminum oxide. Meanwhile, among the chemical reactions by which aluminum oxide is produced from organoaluminum compounds, the simplest is the thermal decomposition reaction. In other words, by simply heating a collection of fine crystals of an organoaluminum compound, the organoaluminum compound is thermally decomposed and aluminum oxide is precipitated. Furthermore, if the organoaluminum compound is easy to synthesize, it can be produced inexpensively. An organoaluminum compound that has both of these properties is an aluminum carboxylate compound. That is, among the substances that constitute the aluminum carboxylate compound, the substance with the largest covalent bond radius is the aluminum ion. On the other hand, in the aluminum carboxylate compound in which the aluminum ion is covalently bonded to the oxygen ion that constitutes the carboxyl group, the distance between the aluminum ion and the oxygen ion is the largest, as in the metal carboxylate compound described in paragraphs 22-23. When an aluminum carboxylate compound with such molecular structure characteristics is heated, it decomposes into carboxylic acid and aluminum at the boiling point of the carboxylic acid. When the temperature is further increased, the carboxylic acid takes the heat of vaporization and vaporizes, and aluminum precipitates after the vaporization of the carboxylic acid is completed. Therefore, an aluminum carboxylate compound that precipitates aluminum oxide by thermal decomposition must have a molecular structure characteristic in which the distance between the oxygen ion that bonds with the aluminum ion is short, and the distance between the oxygen ion and the ion that bonds with the ion on the opposite side of the aluminum ion is the longest. In other words, when an aluminum carboxylate compound is heated, the site where the oxygen ion bonds with the ion that bonds with the ion on the opposite side of the aluminum ion breaks first at the boiling point of the carboxylic acid, and the compound decomposes into aluminum oxide and carboxylic acid. Among the aluminum carboxylate compounds with such molecular structure characteristics are those in which the oxygen ions constituting the carboxyl group act as ligands and approach aluminum ions to form coordinate bonds. Furthermore, aluminum carboxylate compounds do not dissolve in methanol, but disperse in it. Furthermore, among organic aluminum compounds, aluminum carboxylate compounds are easy to synthesize and inexpensive. That is, when a carboxylic acid is reacted with a strong alkaline solution such as sodium hydroxide, an alkali metal carboxylate compound is produced. When this alkali metal carboxylate compound is reacted with an inorganic aluminum salt such as sulfate, an aluminum carboxylate compound is produced. In addition, since carboxylic acids are organic acids with low boiling points, their thermal decomposition temperatures are relatively low. For this reason, aluminum carboxylate compounds, in which oxygen ions constituting the carboxyl group act as ligands and approach aluminum ions to form coordinate bonds, are inexpensive industrial chemicals and the heat treatment costs are also low. Metal carboxylate compounds with these molecular structure characteristics include metal acetate compounds, metal caprylate compounds, metal benzoate compounds, and metal naphthenate compounds. The boiling points of acetic acid are 118°C, caprylate compounds 237°C, and benzoate compounds 249°C. Naphthenic acid, on the other hand, is a mixture of saturated fatty acids with five-membered rings, and has the general formula C n H 2n-1 It is represented by COOH, and the main component is C 9 H 17 It consists of COOH. The thermal decomposition temperature of metal naphthenate is 330°C. In addition, alkane C 20 H 42 The boiling point of the metal compound is 344° C. Therefore, the metal acetate compound, the metal caprylate compound, the metal benzoate compound, and the metal naphthenate compound have both of the above-mentioned properties. On the other hand, aluminum benzoate is a desirable aluminum carboxylate compound that precipitates aluminum oxide through thermal decomposition. That is, aluminum acetate and aluminum caprylate precipitate amorphous alumina through thermal decomposition. Aluminum naphthenate completes its thermal decomposition at 330°C. Therefore, aluminum benzoate Al(C), which has a thermal decomposition temperature 20°C lower than that of aluminum naphthenate, is the most suitable. 6 H 5 COO) 3 However, it is preferable as a source of aluminum oxide.
[0026] EMBODIMENT 2 This embodiment relates to the carboxylate copper compound that releases copper by thermal decomposition described in paragraphs 22 and 23. The carboxylate copper compound of the present invention has two properties: first, it is dispersed in methanol but is not dissolved in methanol, and second, it precipitates copper by thermal decomposition. Ammine copper complexes and chloro copper complexes are examples of complexes that contain copper complex ions in which inorganic molecules or inorganic ions with low molecular weights are coordinately bonded to copper ions. These complexes precipitate copper by thermal decomposition in a reducing atmosphere, but are more expensive than organocopper compounds made from general-purpose organic acids. Organocopper compounds precipitate copper. Among the chemical reactions by which copper is produced from organocopper compounds, thermal decomposition is one of the simplest. Furthermore, if the organic acid is a general-purpose organic acid and the organocopper compound is easy to synthesize, the organocopper compound can be produced at low cost. Furthermore, if the thermal decomposition temperature of the organocopper compound is low, copper can be precipitated at low heat treatment costs. Organocopper compounds that have both of these properties include the carboxylate anion (R-COO - ) is covalently bonded to a copper ion. In other words, the largest ion among the ions that make up the copper carboxylate is the copper ion. Therefore, if the carboxylate anion of the carboxylic acid is covalently bonded to the copper ion, the distance between the copper ion and the carboxylate anion is the longest among the distances between ions. When such a copper carboxylate is heated in an air atmosphere, it decomposes into the carboxylic acid and copper when it exceeds the boiling point of the carboxylic acid. When it is further heated, if the carboxylic acid is composed of a saturated fatty acid, the carboxylic acid vaporizes with the heat of vaporization, and copper precipitates after the carboxylic acid vaporizes. Note that the thermal decomposition of copper carboxylate in a nitrogen atmosphere proceeds at a higher temperature than that in an air atmosphere, so the thermal decomposition in an air atmosphere requires less heat treatment. Also, if the carboxylic acid is an unsaturated fatty acid, the carbon atoms become excessive relative to the hydrogen atoms, and copper oxide precipitates when the copper carboxylate composed of the unsaturated fatty acid is thermally decomposed. On the other hand, in copper carboxylates, the carboxylate anion of the carboxylic acid acts as a ligand and approaches the copper ion to form a coordinate bond, resulting in a short distance between the copper ion and the carboxylate anion, while the distance between the oxygen ion in the carboxylate anion and the ion bonded on the opposite side to the copper ion is the longest. In the thermal decomposition reaction of copper carboxylates having such molecular structure, the bond between the oxygen ion in the carboxylate anion and the ion bonded on the opposite side to the copper ion is first broken, resulting in the precipitation of copper oxide. This copper carboxylate belongs to the carboxylate metal compound described in the first embodiment. Furthermore, copper carboxylates are the easiest to synthesize and the least expensive organic copper compounds because carboxylic acids are the most widely used organic acids. In other words, when carboxylic acids are reacted in a strong alkaline solution such as sodium hydroxide, an alkali metal carboxylate compound is produced. When this alkali metal carboxylate compound is reacted with an inorganic copper compound such as copper sulfate, copper carboxylate is produced. For this reason, copper carboxylates are the least expensive of the organic copper compounds. The formula for copper carboxylate is Cu(COOR) 2 R is a hydrocarbon, and the formula is C m H n (where m and n are integers). Among the substances that make up copper carboxylate, the copper ion Cu, which is located in the center of the composition formula, 2+ Therefore, copper ions Cu 2+ and carboxylate anion (R-CO 2 - ) is covalently bonded to copper ion Cu 2+ and carboxylate anion (R-CO 2 - ) is the longest. This is because the covalent bond radius of the double bond of the copper atom is 115 pm, the covalent bond radius of the double bond of the oxygen atom is 57 pm, and the covalent bond radius of the double bond of the carbon atom is 67 pm. Therefore, when the boiling point of the carboxylic acid is exceeded, the copper ion with the longest bond distance and the carboxylate anion (R-CO) are bonded together. 2 -) is first broken, separating the copper from the carboxylic acid. If the temperature is further increased, if the carboxylic acid is a saturated fatty acid, the carboxylic acid will vaporize with the heat of vaporization, and the copper will precipitate after the vaporization of the carboxylic acid is complete. Examples of such copper carboxylates include copper octylate, copper laurate, and copper stearate. Many of these copper carboxylates are inexpensive industrial chemicals sold commercially as metal soaps. Furthermore, if the boiling point of the saturated fatty acid is low, the carboxylate copper will decompose at a low temperature, and the cost of heat treatment to precipitate the copper will be low. If the hydrocarbons that make up the saturated fatty acid have a long-chain structure, the longer the chain, that is, the higher the molecular weight of the saturated fatty acid, the higher the boiling point of the saturated fatty acid will be, and the greater the heat of vaporization of the saturated fatty acid, the higher the thermal decomposition temperature. Incidentally, the boiling point of lauric acid, which has a molecular weight of 200.3, at atmospheric pressure is 296°C, and the boiling point of stearic acid, which has a molecular weight of 284.5, at atmospheric pressure is 361°C. In contrast, saturated fatty acids with a branched chain structure have shorter chain lengths than saturated fatty acids with a straight chain structure, resulting in a lower boiling point and a smaller heat of vaporization. For this reason, copper carboxylates made from saturated fatty acids with a branched chain structure undergo thermal decomposition at an even lower temperature. In addition, because saturated fatty acids with a branched chain structure are polar, copper carboxylates made from saturated fatty acids with a branched chain structure also have polarity, and disperse at a relatively high rate in polar organic solvents such as methanol. Octylic acid is an example of such a branched saturated fatty acid. Octylic acid has the structural formula CH 3 (CH 2 ) 3 CH(C 2 H 5 )COOH and CH 3 (CH 2 ) 3 and C. 2 H 5 The alkane is branched into CH and COOH, and the carboxyl group COOH is bonded to CH. The boiling point of octylic acid at atmospheric pressure is 228°C, which is 68°C lower than that of lauric acid. For this reason, copper octylate Cu(C 7 H 15 COO) 2Copper octylate is decomposed at 290℃ in air and copper is precipitated, and it is dispersed in methanol at about 10% by weight. In a nitrogen atmosphere, the decomposition is completed at 340℃ and copper is precipitated.
[0027] Example 1 In this embodiment, a graphene joint in which overlapping graphene particles are joined together is formed on the bottom surface of the container according to the processing methods described in the first and second steps described in paragraph 13. First, 2 liters of 1-butanol was filled into a shallow container with a base dimension of 1.2 m x 1.2 m. Next, two parallel flat electrode plates with an effective area of 1m x 1m are prepared, in which an electric field is generated in the gap between the two parallel flat electrode plates. The two parallel flat electrode plates are stacked with a gap of 100μm between them, and graphite particles are evenly packed into the gap, which is then immersed in 1-butanol. Note that, assuming that the graphite particles are spheres with a particle size of 25μm, when the graphite particles are evenly packed into the 100μm gap created by the two parallel flat electrode plates, the electric field of 6.4×10 7 When a DC voltage of 10.6 kV or more is applied to this collection of graphite particles, the interlayer bonds on the basal planes of all the graphite particles are simultaneously destroyed. 13 A cluster of graphene is obtained, and the cluster of graphite particles used weighs only 1.18 g. For this purpose, 6 g of flake graphite particles (e.g., XD100 from Ito Graphite Industries Co., Ltd.) were piled up and packed on the surface of a parallel plate electrode plate with an effective area of 1 m x 1 m where an electric field is generated. This parallel plate electrode plate was immersed in a container filled with 1-butanol, and another parallel plate electrode plate was placed on top of the above parallel plate electrode plate, and the two parallel plate electrodes were separated by a gap of 100 μm, and a direct current voltage of 12 kilovolts was applied between the electrodes. Next, the gap between the two parallel plate electrodes was enlarged, and the two parallel plate electrodes were tilted in 1-butanol, and vibration accelerations of 0.2 G in three directions were repeatedly applied to the container, after which the two parallel plate electrodes were taken out of the container. Next, 81 g of the dispersion liquid in which the graphene clusters were dispersed in 1-butanol was transferred to a container measuring 30 cm x 30 cm x 1 cm (depth). After this, vibration acceleration of 0.2 G in three directions was applied to the container three times for 5 seconds each. Furthermore, the container was heated to 117°C, and the 1-butanol in the container was evaporated. After this, an aluminum plate measuring 30 cm x 30 cm x 1 mm (thickness) was placed on the surface of the sample in the container. Furthermore, nine weights of 10 kg were placed at equal intervals on the aluminum plate, and the surface of the sample was compressed evenly. After this, the weights and the aluminum plate were removed. Two such samples were made. For one sample, an impact acceleration of 0.5 G was applied simultaneously three times to five points on the bottom surface of the container, the sample was peeled off from the bottom of the container, and the sample was removed from the container. Next, the surface and side of the sample were observed and analyzed using an electron microscope. An extremely low accelerating voltage SEM from JFE Techno-Research Corporation was used as the electron microscope. This device allows surface observation at extremely low accelerating voltages starting from 100 volts, and has the advantage of allowing the surface of the sample to be observed directly without forming a conductive coating on the sample. First, a secondary electron beam between 900-1000 volts reflected from the surface of the sample was extracted and image-processed. Extremely thin steps were confirmed on the surface of the sample. Next, a secondary electron beam between 900-1000 volts reflected from the side of the sample was extracted and image-processed. Approximately 20 layers of extremely thin material were stacked on top of each other. Furthermore, image-processing of the energy and intensity of the characteristic X-rays confirmed that only carbon atoms were present, and that the sample was a graphene junction in which graphene was stacked on top of each other. Figure 1 shows a schematic diagram of a graphene joint in which graphene sheets are overlapped and joined, with a partially enlarged side view. 1 is graphene. Furthermore, nine 10 kg weights were placed again on the graphene conjugated body peeled off from the bottom of the container, via a 30 cm × 30 cm × 1 mm aluminum plate, and after the weights and the aluminum plate were removed, the surface of the graphene conjugated body was observed again under the electron microscope. No change was found on the surface of the graphene conjugated body, indicating that the graphene particles are bonded together with a certain bonding force.
[0028] Example 2 In this example, the insulating layer is prepared according to the process described in the third step in paragraph 13. Aluminum benzoate Al(C) is used as a raw material for aluminum oxide. 6 H 5 COO) 3 (For example, products from Mitsuwa Chemical Co., Ltd.) were used. 3.9g (corresponding to 0.01 mole) of aluminum benzoate was dispersed in 50g of methanol to prepare a methanol dispersion of aluminum benzoate. 10g of the methanol dispersion of aluminum benzoate was poured into a container having an outer square pillar of 20cm x 20cm x 2cm, an inner square pillar of 16cm x 16cm x 2cm, and a groove of 2cm width and 1cm depth sandwiched between the two square pillars. After this, the container was heated to 65°C, and the methanol in the container was vaporized. Furthermore, vibration acceleration of 0.3G in three directions was applied to the container three times for 5 seconds each. After this, an aluminum plate having an outer square pillar of 20cm x 20cm x 2cm, an inner square pillar of 16cm x 16cm x 2cm, a width of 2cm sandwiched between the two square pillars, and a thickness of 1mm was placed on the surface of the methanol dispersion in the container. Furthermore, nine 4 kg weights were placed at equal intervals on the aluminum plate, the surface of the sample was evenly compressed, and the weights were removed after 10 seconds. After this, the container was placed in a heat treatment device heated to 200°C in an air atmosphere. First, the heat treatment device was heated to 240°C at a heating rate of 20°C / min, then heated to 310°C at a heating rate of 70°C / min, left at 310°C for 1 minute, and the container was removed from the heat treatment device. After this, nine 8 kg weights were placed at equal intervals on the aluminum plate, the surface of the sample was evenly compressed, and the weights were removed after 10 seconds. Furthermore, an impact acceleration of 0.4G was applied simultaneously three times to four points on the bottom of the container, and the sample was peeled off from the bottom of the container. Two such samples were prepared. Next, the surface and side of the sample were observed and analyzed using the electron microscope used in Example 1. First, a secondary electron beam between 900-1000V of the reflected electron beam from the surface was extracted and image processed. The sample had granular nanoparticles with a size of about 10 nm bonded together at a high density. Next, the energy between 900-1000V of the reflected electron beam was extracted and image processed, and the difference in material was observed based on the shading of the image. Since shading was observed, the nanoparticles were formed from multiple atoms. Furthermore, the energy and intensity of the characteristic X-rays were image processed, and the elements that make up the nanoparticles were analyzed. Since aluminum atoms and oxygen atoms were present, the nanoparticles were aluminum oxide nanoparticles. In addition, secondary electron beams between 900-1000V of the reflected electron beam from the side were extracted and image processing was performed. The sample was made up of about 10 granular nanoparticles with a size of about 10 nm stacked together. Therefore, the sample created had aluminum oxide nanoparticles with a size of about 10 nm joined together to form an insulating layer with a thickness of about 100 nm. Next, the insulation resistance of the sample peeled off from the bottom of the container was measured using an insulation resistance meter IR4055 made by Hioki E.E. Corporation. The insulation resistance exceeded 100 MΩ, demonstrating high insulation properties. Furthermore, nine 8 kg weights were again placed on the sample peeled off from the bottom of the container, via the aluminum plate described above, and after the weights and aluminum plate were removed, the surface of the sample was observed again under the electron microscope; no change was found on the surface of the sample, indicating that the aluminum oxide nanoparticles are bonded together with a certain adhesive force.
[0029] Example 3 In this example, the conductive layer is prepared according to the process described in the fourth step in paragraph 13. As a raw material for copper, copper octylate Cu(C 7 H 15 COO) 2 (For example, products from Mitsuwa Chemical Co., Ltd.) were used. 5.3g (corresponding to 0.015 moles) of copper octylate was dispersed in 60g of methanol to prepare a methanol dispersion of copper octylate. 15g of the methanol dispersion of copper octylate was poured into a container in which an outer rectangular pillar was 19cm x 19cm x 2cm, an inner rectangular pillar was 17cm x 17cm x 2cm, and a groove having a width of 1cm and a depth of 1cm was formed between the two rectangular pillars. After this, the container was heated to 65°C, and the methanol in the container was evaporated. Furthermore, the container was placed in a heat treatment device heated to 200°C in the air atmosphere. First, the heat treatment device was heated to 220°C at a heating rate of 20°C / min, then heated to 290°C at a heating rate of 70°C / min, and left at 290°C for 1 minute, and the container was removed from the heat treatment device. After this, an impact acceleration of 0.3G was applied three times simultaneously to four points on the bottom of the container, and the sample was peeled off from the bottom of the container. Two such samples were produced. Next, the surface and side of the sample were observed and analyzed using the electron microscope used in Example 1. First, a secondary electron beam between 900-1000V of the reflected electron beam from the surface was extracted and image processed. The sample had granular nanoparticles with a size of 40-60 nm bonded together at a high density. Next, the energy between 900-1000V of the reflected electron beam was extracted and image processed, and the difference in material was observed based on the shading of the image. Since no shading was observed, the nanoparticles were formed from a single atom. Furthermore, the energy and intensity of the characteristic X-rays were image processed, and the elements that make up the nanoparticles were analyzed. Since only copper atoms were present, the nanoparticles were copper nanoparticles. In addition, secondary electron beams between 900-1000V of the reflected electron beam from the side were extracted and image processing was performed. The sample was made up of about 20 stacked granular nanoparticles with a size of 40-60nm. Therefore, the sample created had copper nanoparticles of 40-60nm bonded together to form an insulating layer with a thickness of about 1μm. Next, the surface resistance of the sample peeled off from the bottom of the container was measured using a surface resistance meter (e.g., a surface resistance meter ST-4 from SIMCO Japan Co., Ltd.). The surface resistance value was 1×10 3Since the value was less than Ω / □, the conductive layer had a surface resistance close to that of a metal. In addition, four 2 kg weights were placed on the sample peeled from the bottom of the container, with the aluminum plate between them. After removing the weights and the aluminum plate, the surface of the sample was observed again under an electron microscope. No change was found on the surface of the sample, indicating that the copper nanoparticles are bonded together with a certain adhesive force.
[0030] Example 4 In this example, a circuit component is produced by friction-welding the insulating layer produced in Example 2 to the surface of the graphene conjugate produced in Example 1, and further friction-welding the conductive layer produced in Example 3 to the surface of the insulating layer, according to the processing method described in the fifth step described in paragraph 13. The insulating layer prepared in Example 2 was placed in the center of the surface of the graphene conjugate of 30 cm x 30 cm prepared in Example 1, the aluminum plate used in Example 2 was placed on the insulating layer, nine weights of 7 kg were placed at equal intervals on the aluminum plate, the surface of the insulating layer was evenly compressed, and the weights were removed after 10 seconds. Furthermore, the conductive layer prepared in Example 3 was placed in the center of the surface of the insulating layer prepared in Example 2, a new aluminum plate material was placed on the surface of the conductive layer, and nine weights of 6 kg were placed at equal intervals on the new plate material, the surface of the conductive layer was evenly compressed, and the weights were removed after 10 seconds. After this, an impact acceleration of 0.5 G was applied three times simultaneously to four points on the bottom surface of the container on which the graphene conjugate was formed, and the sample was peeled off from the bottom of the container. Two such samples were prepared. Figure 2 shows a front view of the first circuit component in which an insulating layer and a conductive layer are friction-welded to the graphene surface of a circuit board. 2 is the graphene conjugate serving as the circuit board, 3 is the insulating layer made of a collection of aluminum oxide nanoparticles, and 4 is the conductive layer made of a collection of copper nanoparticles. Nine 7 kg weights were placed at equal intervals on the surface of one of the samples to which the conductive layer was bonded, but there was no change in the conductive layer and the insulating layer. Furthermore, nine 8 kg weights were placed at equal intervals on the surface of the sample to which the conductive layer was bonded. During this process, the conductive layer was compressed very slightly and plastically deformed, but neither the insulating layer nor the conductive layer peeled off from the graphene conjugate. Therefore, the insulating layer was bonded to the graphene conjugate with a certain bonding strength, and the conductive layer was bonded to the insulating layer with a certain bonding strength. Furthermore, the other sample was allowed to fall from a height of 2 m, but no change was observed. Furthermore, the sample was allowed to fall from a height of 4 m, but no change was observed. Therefore, the insulating layer was bonded to the graphene composite with a certain bonding strength, and the conductive layer was bonded to the insulating layer with a certain bonding strength.
[0031] Example 5 In this embodiment, graphene conjugates of the same shape are formed by bonding overlapping graphene together on the bottom surface of each of a plurality of grooves formed in a container according to the processing methods described in the first and second steps described in paragraph 18. First, a container is prepared by forming ten grooves, each measuring 11 cm x 2 cm x 1 cm (depth), with two grooves in the horizontal direction and five grooves in the vertical direction, spaced 2 cm apart, in a 28 cm x 22 cm x 1.5 cm (thickness) board, with the grooves formed 2 cm away from each end of the container.Furthermore, a 28 cm x 22 cm x 2.5 cm (thickness) board is prepared with ten protrusions, each measuring 11 cm x 2 cm x 1.5 mm (length), in positions where the sides of the ten protrusions will come into contact with the sides of the ten grooves when the board is placed over the container. Figure 3 shows a front view of a container for forming ten second circuit components by friction-welding an insulating layer and a conductive layer onto the graphene surface of a circuit board. 5 denotes ten grooves of the same shape and size for forming the circuit components. Next, 2 g of the dispersion liquid in which the graphene clusters prepared in Example 1 were dispersed in 1-butanol was injected into each of the 10 grooves. After this, vibration acceleration of 0.2 G in three directions was applied to the container for 5 seconds three times each. Furthermore, the container was heated to 117°C, and the 1-butanol in each of the 10 grooves was vaporized. After this, a plate material was stacked on the surface of the container, and 10 protrusions were inserted into each of the 10 grooves. Furthermore, five 12 kg weights were placed at equal intervals on the plate material, and the surface of the sample was compressed evenly. After this, the weights and the aluminum plate were removed. Ten such samples were produced.
[0032] Example 6 In this embodiment, an insulating layer is formed on the bottom surface of each of a plurality of grooves formed in a container according to the processing method described in the third step in paragraph 18. First, a container is prepared by forming 10 grooves, each 1 cm in diameter and 1 cm deep, with 2 grooves in the horizontal direction and 5 grooves in the vertical direction, spaced 1 cm apart, in a 5 cm x 11 cm x 1.5 cm (thickness) plate, and forming grooves 1 cm away from each of the four edges of the container.Furthermore, a 5 cm x 11 cm x 2.5 cm (thickness) plate is prepared with 10 protrusions, each 1 cm in diameter and 1.5 cm in length, in positions where the sides of the 10 protrusions will come into contact with the sides of the 10 grooves when the plate is placed over the container. Next, 0.07 g of the methanol dispersion of aluminum benzoate prepared in Example 2 was poured into each of the 10 grooves. After this, the container was heated to 65°C, and the methanol in the container was evaporated. After this, the plate material was stacked on the container, and five 1 kg weights were placed at equal intervals on the plate material to evenly compress the surface of the sample, and the weights were removed after 10 seconds. After this, the container was placed in a heat treatment device heated to 200°C in an air atmosphere. First, the heat treatment device was heated to 240°C at a heating rate of 20°C / min, then heated to 310°C at a heating rate of 70°C / min, and left at 310°C for 1 minute, and the container was removed from the heat treatment device. After this, five 2 kg weights were placed at equal intervals on the aluminum plate, and the surface of the sample was evenly compressed, and the weights were removed after 10 seconds. In addition, an impact acceleration of 0.4G was applied three times simultaneously to five points on the bottom of the container, and the sample was peeled off from the bottom of the container. Ten such samples were created.
[0033] Example 7 In this embodiment, a conductive layer is formed on the bottom surface of each of a plurality of grooves formed in a container according to the processing method described in the fourth step in paragraph 18. First, a container is prepared by forming ten grooves, each 0.8 cm in diameter and 1 cm deep, two in the horizontal direction and five in the vertical direction, spaced 0.8 cm apart in a 3.2 cm x 8.8 cm x 1.5 cm (thickness) plate, with the grooves formed 0.8 cm away from each other on all four edges of the container.Furthermore, a 3.2 cm x 8.8 cm x 2.5 cm (thickness) plate is prepared with ten protrusions, each 0.8 cm in diameter and 1.5 cm in length, formed in positions where the sides of the ten protrusions will come into contact with the sides of the ten grooves when the plate is placed over the container. Next, 0.04 g of the methanol dispersion of copper octylate prepared in Example 3 was poured into each of the grooves in the same amount. After this, the container was heated to 65°C, and the methanol in the container was evaporated. Furthermore, the container was placed in a heat treatment device heated to 200°C in an air atmosphere. First, the heat treatment device was heated to 220°C at a heating rate of 20°C / min, then heated to 290°C at a heating rate of 70°C / min, and left at 290°C for 1 minute, and the container was removed from the heat treatment device. After this, an impact acceleration of 0.3 G was applied three times simultaneously to four points on the bottom of the container, and the sample was peeled off from the bottom of the container. Ten such samples were made.
[0034] Example 8 In this example, according to the processing method described in the fifth step described in paragraph 18, the insulating layer prepared in Example 6 is friction-welded to the same position on the surface of the graphene conjugate prepared in each of the 10 grooves prepared in Example 5, and further, the conductive layer prepared in Example 7 is friction-welded to the same position on the surface of the insulating layer, thereby creating circuit components having the same shape and the same configuration in each of the 10 grooves. Ten insulating layers prepared in Example 6 were arranged at equal intervals on the surface of the graphene conjugates made in each of the ten grooves made in Example 5, the plate material used in Example 5 was placed on the surface, five weights of 2 kg were placed on the plate material at equal intervals, the surface of the insulating layer was compressed evenly, and the weights were removed after 10 seconds. Furthermore, the conductive layer prepared in Example 7 was placed on the center of the surface of each of the ten insulating layers, the plate material used in Example 5 was placed on the surface, five weights of 1.5 kg were placed on the plate material at equal intervals, the surface of the conductive layer was compressed evenly, and the weights were removed after 10 seconds. After this, an impact acceleration of 0.5 G was applied three times simultaneously to four points on the bottom surface of the container on which the graphene conjugates were formed, and the sample was peeled off from the bottom of the container. Ten such samples were prepared. Five 1.5 kg weights were placed at equal intervals on the surface of one of the samples to which the conductive layer was bonded, but there was no change in the conductive layer and the insulating layer. Furthermore, five 2 kg weights were placed at equal intervals on the surface of the sample to which the conductive layer was bonded. At this time, the conductive layer was compressed very slightly and plastically deformed, but neither the insulating layer nor the conductive layer peeled off from the graphene conjugate. Therefore, the insulating layer was bonded to the graphene conjugate with a certain bonding strength, and the conductive layer was bonded to the insulating layer with a certain bonding strength. Furthermore, the other sample was allowed to fall from a height of 2 m, but no change was observed. Furthermore, the sample was allowed to fall from a height of 4 m, but no change was observed. Therefore, the insulating layer was bonded to the graphene composite with a certain bonding strength, and the conductive layer was bonded to the insulating layer with a certain bonding strength.
[0035] The graphene conjugates produced in Examples 1 and 5 are merely examples. In other words, the shape of the graphene conjugate and the number of graphene sheets laminated and bonded are determined by the shape of a container into which a dispersion liquid in which graphene clusters are dispersed in 1-butanol is poured and the amount poured. On the other hand, there are no restrictions on the shape of the container and the amount poured. Therefore, there are no restrictions on the shape of the graphene conjugate and the number of graphene sheets laminated and bonded. Furthermore, graphene is an extremely tough material, and even if excessive compressive stress is applied to a graphene cluster in which graphene clusters are overlapped, the graphene does not break. Therefore, when excessive compressive stress is applied to overlapping graphene clusters, frictional heat is generated at the overlapping portions, and the graphene clusters are bonded together by the frictional heat. Therefore, the graphene conjugates produced in Examples 1 and 5 are merely examples. The shape and thickness of the insulating layer created in Example 2 and Example 6 are determined by the shape of the container into which the methanol dispersion of aluminum benzoate is poured and the amount poured. On the other hand, there are no restrictions on the shape of the container and the amount poured. Therefore, there are no restrictions on the shape and thickness of the insulating layer. Therefore, the insulating layers created in Example 2 and Example 6 are merely examples. Therefore, the insulation resistance of the insulating layer can be freely changed. The shape and thickness of the conductive layer created in Example 3 and Example 7 are determined by the shape of the container into which the methanol dispersion of copper octylate is poured and the amount poured. On the other hand, there are no restrictions on the shape of the container and the amount poured. Therefore, there are no restrictions on the shape and thickness of the conductive layer. Therefore, the insulating layers created in Examples 2 and 6 are merely examples. Furthermore, in the circuit component produced in Example 4, the insulating layer produced in Example 2 is friction-welded to the surface of the graphene conjugate produced in Example 1, and further, the conductive layer produced in Example 3 is friction-welded to the surface of the insulating layer, so that the shape and configuration of the circuit component produced in Example 4 are merely an example. Similarly, the shape and configuration of the circuit component produced in Example 8 are also merely an example. [Explanation of symbols]
[0036] 1 Graphene 2 Graphene junction as a circuit substrate 3 Insulating layer made of aluminum oxide nanoparticles 4 Conductive layer made of copper nanoparticles 5 Grooves for creating circuit components
Claims
1. A method for producing a circuit component in which a graphene joint obtained by friction welding graphene particles together is used as a circuit board, an insulating layer made of an assembly of fine particles of insulating metal oxide in which fine particles of the metal oxide are friction-welded to a surface of the circuit board, and a conductive layer made of an assembly of fine metal particles in which fine metal particles are metallically bonded to each other is friction-welded to the surface of the insulating layer, comprises the steps of: A collection of flake graphite particles or a collection of lump graphite particles is spread evenly on the surface of one of two parallel plate electrodes, the one parallel plate electrode is immersed in 1-butanol filled in a first container, and the other parallel plate electrode is placed on top of the one parallel plate electrode, the two parallel plate electrodes are separated by the collection of flake graphite particles or the collection of lump graphite particles, and the two separated parallel plate electrodes are immersed in the 1-butanol. Thereafter, a direct current potential difference having a predetermined magnitude is applied to the gap between the two parallel plate electrodes, whereby an electric field equivalent to the value obtained by dividing the magnitude of the potential difference by the size of the gap between the two parallel plate electrodes is generated between the collection of flake graphite particles or the lump graphite particles. a first process of producing graphene aggregates in a container from a collection of graphite particles, the first process comprising applying a voltage to a collection of graphite particles having a diameter of about 100 nm to a first container, so that all interlayer bonds of the basal planes forming the flake-like graphite particles or the lump-like graphite particles are simultaneously broken, and a collection of graphene corresponding to the basal planes is precipitated in the gap between the two parallel plate electrodes, thereafter the gap between the two parallel plate electrodes is enlarged, the two parallel plate electrodes are tilted in the 1-butanol, and vibration accelerations in three directions, left-right, front-back, and up-down, are applied to the first container to move the collection of graphene from the gap between the two parallel plate electrodes into the 1-butanol and disperse the collection of graphene in the 1-butanol, and the two parallel plate electrodes are removed from the first container; A predetermined amount of the graphene aggregates dispersed in the 1-butanol is poured from the first container into a second container having a bottom shape corresponding to a shape of a circuit board, and a vibration acceleration in three directions, i.e., front-back, left-right, and up-down, is repeatedly applied to the second container as a vibration acceleration greater than the vibration acceleration applied in the first step, so that the graphene aggregates are aligned in a planar shape in the 1-butanol, and the graphene aggregates aligned in a planar shape are stacked one on top of the other via the 1-butanol to form the graphene aggregates in the second container; and further, the temperature of the second container is raised to the boiling point of the 1-butanol to extract the 1-butanol from the graphene aggregates. a second step of forming a graphene conjugate having the shape of the bottom surface of the container as a circuit board on a bottom surface of the container, the second step being a process of removing the plate from the second container; and a second step of forming a graphene conjugate having the shape of the bottom surface of the container as a circuit board on a bottom surface of the container, the second step being a process of removing the plate from the second container; a first metal compound having both a first property of precipitating a metal oxide by thermal decomposition in an air atmosphere and a second property of dispersing in methanol is dispersed in methanol to prepare a methanol dispersion, a predetermined amount of the methanol dispersion of the first metal compound is poured into a third container having a bottom shape that is the same as the shape of an insulating layer, the third container is then heated to the boiling point of methanol to precipitate a cluster of fine crystals of the first metal compound from the methanol dispersion of the first metal compound, the third container is then covered with a plate material that covers the entire surface of the cluster of fine crystals of the first metal compound, and the entire surface of the plate material is uniformly compressed with a compressive force smaller than that applied to the plate material in the second step to crush the cluster of fine crystals of the first metal compound and prepare a cluster of crystals finer than the fine crystals, a third step of forming an insulating layer on the bottom surface of the third container in the shape of the bottom surface of the container, the third step being performed by repeatedly applying vertical impact acceleration to the bottom surface of the third container to peel off the insulating layer from the bottom surface of the third container; the third step of forming an insulating layer on the bottom surface of the container in the shape of the bottom surface of the container, the third step being performed by repeatedly applying vertical impact acceleration to the bottom surface of the third container to peel off the insulating layer from the bottom surface of the third container; A second metal compound having both a first property of precipitating a metal by thermal decomposition in an air atmosphere and a second property of dispersing in methanol is dispersed in methanol to prepare a methanol dispersion, a predetermined amount of the methanol dispersion of the second metal compound is poured into a fourth container having a bottom shape that corresponds to the shape of the conductive layer, the fourth container is then heated to the boiling point of methanol to precipitate a collection of fine crystals of the second metal compound from the methanol dispersion of the second metal compound, and the fourth container is further heated to a temperature at which the second metal compound is thermally decomposed, thereby producing a metal. a fourth step of forming a conductive layer consisting of a collection of metal particles bonded together by metallic bonding on the bottom surface of the fourth container in the shape of the bottom surface of the container, the conductive layer consisting of a collection of metal particles bonded together by metallic bonding being formed on the bottom surface of the fourth container in the shape of the bottom surface of the container, the fourth step being a process of repeatedly applying to the bottom surface of the fourth container an impact acceleration in the vertical direction that is smaller than the impact acceleration applied to the bottom surface of the third container, and peeling off the conductive layer from the bottom surface of the fourth container; The insulating layer formed in the third step is superimposed on a predetermined position of the circuit board formed in the second step, a plate material is placed over the insulating layer to cover the entire surface of the insulating layer, and the entire surface of the plate material is evenly compressed with a compressive force smaller than the compressive force applied when bonding the metal oxide fine particles to each other by frictional heat in the third step, and the contact portion between the circuit board and the insulating layer is frictionally welded to bond the insulating layer to the circuit board. Thereafter, the plate material is removed from the insulating layer, and the conductive layer formed in the fourth step is superimposed on a predetermined position of the insulating layer, a new plate material is placed over the insulating layer to cover the entire surface of the conductive layer, and the insulating layer is frictionally welded to the circuit board. a fifth step of manufacturing a circuit component in which an insulating layer and a conductive layer are frictionally welded to a circuit board, the fifth step comprising a process of uniformly compressing the entire surface of the new plate material with a compressive force smaller than the compressive force applied when the new plate material was brought into contact with the insulating layer, frictionally welding the contact portions between the conductive layer and the insulating layer, and bonding the conductive layer to the insulating layer, after which the new plate material is removed from the conductive layer, and repeatedly applying vertical impact accelerations greater than the impact acceleration applied to the bottom surface of the third container to the bottom surface of the second container on which the circuit board is formed, thereby peeling off the circuit component in which the insulating layer and the conductive layer are bonded to the circuit board, from the bottom surface of the second container; The method for continuously carrying out the treatment consisting of the five steps includes using a graphene joint formed by friction welding graphene particles together as a circuit board, friction-welding an insulating layer made of an assembly of fine particles of insulating metal oxide formed by friction-welding fine particles of the metal oxide together onto a surface of the circuit board, and further friction-welding a conductive layer made of an assembly of fine particles of metal oxide formed by metallic bonding of fine particles of the metal oxide together onto the surface of the insulating layer, to produce a circuit component in which the insulating layer and the conductive layer are friction-welded onto the surface of the circuit board.
2. The method for manufacturing a circuit component according to claim 1 is a method for simultaneously manufacturing a plurality of circuit components having the same configuration, the method for simultaneously manufacturing a plurality of circuit components comprising the steps of: A plurality of grooves having the same shape are formed in the second container described in the second step of claim 1, and the same amount of the graphene clusters dispersed in 1-butanol described in the first step of claim 1 is poured into each of the plurality of grooves, and vibration acceleration in three directions is repeatedly applied to the second container, so that the graphene clusters are aligned in a planar shape in the 1-butanol, and the graphene clusters aligned in a planar shape are stacked by overlapping each other via the 1-butanol to form the graphene clusters in each of the plurality of grooves, thereafter, the temperature of the second container is raised to the boiling point of 1-butanol to vaporize the 1-butanol from the plurality of grooves, and the graphene clusters in which the graphene clusters overlap each other are formed on the bottom surface of each of the plurality of grooves, and further, the plate material described in the second step of claim 1 has a plurality of protrusions having the same shape, a first step of simultaneously forming a plurality of graphene conjugates of the same shape on the bottom surface of each of the plurality of grooves in the shape of the bottom surface of the plurality of grooves, the first step being a step of preparing a plate material on which the plurality of protrusions are formed, overlapping the surface of the plate material on which the plurality of protrusions are formed with the surface of the second container on which the plurality of grooves are formed, and then evenly compressing the entire surface of the plate material on the opposite side on which the plurality of protrusions are formed, friction-welding the overlapping graphene formed on the bottom surfaces of the grooves, and forming a graphene conjugate consisting of an assembly of graphene joined by the friction welding on the bottom surface of each of the plurality of grooves in the shape of the bottom surface of the plurality of grooves as a circuit board, and then removing the plate material from the second container; A plurality of grooves having the same shape are formed in the third vessel described in the third step of claim 1, and the same amount of the methanol dispersion of the first metal compound described in the third step of claim 1 is poured into each of the plurality of grooves. Thereafter, the temperature of the third vessel is raised to the boiling point of methanol, and methanol is evaporated from each of the plurality of grooves, and a collection of fine crystals of the first metal compound is precipitated in each of the plurality of grooves. Furthermore, the plate material described in the third step of claim 1 has a plurality of protrusions having a plurality of the same shape. a plate material having the plurality of protrusions, the side of the protrusions being in contact with the side of the groove, and the length of the protrusions being longer than the depth of the groove; the plate material having the plurality of protrusions is prepared, the surface of the plate material having the plurality of protrusions is placed on the surface of the third container having the plurality of grooves, and the plurality of protrusions are inserted into the plurality of grooves; thereafter, the entire surface of the plate material opposite to the surface on which the plurality of protrusions are formed is uniformly compressed with a compressive force smaller than the compressive force applied to the plate material in the first step, and the front surface of each of the plurality of grooves is compressed. The clusters of microcrystals of the first metal compound are crushed. Thereafter, the temperature of the third container is raised to a temperature at which the first metal compound is thermally decomposed, and clusters of insulating metal oxide nanoparticles are precipitated. Furthermore, a compressive force greater than the compressive force used when crushing the clusters of microcrystals of the first metal compound is evenly applied to the entire surface of the plate material, compressing the clusters of metal oxide nanoparticles precipitated in each of the plurality of grooves, and frictionally welding the contact portions between the metal oxide fine particles to form the nanoparticles in which the metal oxide fine particles are joined together. a second step of simultaneously forming a plurality of insulating layers of the same shape on the bottom surface of each of the plurality of grooves in the shape of the bottom surface, the second step being a process of simultaneously forming an insulating layer consisting of a collection of insulating particles on the bottom surface of each of the plurality of grooves in the shape of the bottom surface, removing the plate material from the third container, and then repeatedly applying impact acceleration in the vertical direction to a plurality of locations on the bottom surface of the third container corresponding to the portions of the third container where the plurality of grooves are formed, thereby simultaneously peeling off the insulating layer from the bottom surface of each of the plurality of grooves; A plurality of grooves of the same shape are formed in the fourth vessel described in the fourth step of claim 1, and the same amount of the methanol dispersion of the second metal compound described in the fourth step of claim 1 is poured into each of the plurality of grooves. Thereafter, the temperature of the fourth vessel is raised to the boiling point of methanol, and methanol is evaporated from the plurality of grooves, causing a cluster of fine crystals of the second metal compound to precipitate in each of the plurality of grooves. Furthermore, the temperature of the fourth vessel is raised to a temperature at which the second metal compound is thermally decomposed, whereby the cluster of fine metal particles in contact with each other is formed. a third step of simultaneously forming a plurality of conductive layers of the same shape on the bottom surface of each of the plurality of grooves, the conductive layers being precipitated all at once, the metal particles bonding with each other at the contact portions, and a collection of the metal particles bonding with each other at the contact portions, simultaneously forming a conductive layer on the bottom surface of each of the plurality of grooves; thereafter, a vertical impact acceleration smaller than the impact acceleration applied to the bottom surface of the third container is repeatedly applied to a plurality of locations on the bottom surface of the fourth container corresponding to the portions of the fourth container where the plurality of grooves are formed, thereby simultaneously peeling off the conductive layer from the bottom surface of each of the plurality of grooves; The insulating layer created in the second step is disposed at the same predetermined position on the surface of the graphene conjugate formed as the shape of the bottom surface of each of the plurality of grooves created in the first step. Also, the plate material according to the fifth step of claim 1 has a plurality of protrusions having the same shape, the shape of the tip of each of the protrusions has the shape of the insulating layer, the plurality of protrusions are formed at positions that contact the surfaces of the plurality of insulating layers arranged in the plurality of grooves, and have a length that compresses the plurality of insulating layers, and a plate material having the plurality of protrusions is prepared. the plate is placed on a second container in which the plurality of grooves are formed so that tips of the plurality of protrusions come into contact with the plurality of insulating layers, and the entire surface of the plate on the opposite side on which the plurality of protrusions are formed is uniformly compressed with a compressive force smaller than the compressive force applied when bonding metal oxide fine particles to each other by frictional heat in the second step, thereby frictionally bonding the contact portion between the graphene conjugate and the insulating layer, and bonding the insulating layer to the graphene conjugate; thereafter, the plate is removed from the second container; and further, the conductors created in the third step are attached to the same predetermined positions of each of the plurality of insulating layers. and a conductive layer is disposed on the new plate material according to the fifth step of claim 1. The new plate material has a plurality of protrusions having the same shape, the tip shape of the protrusions has the shape of the conductive layer, the plurality of protrusions are formed at positions where they contact the surfaces of the plurality of conductive layers disposed in the plurality of grooves, and have a length that compresses the plurality of conductive layers. A plate material having the plurality of protrusions is prepared, and the plate material is placed on a second container in which the plurality of grooves are formed so that the plurality of protrusions contact the surfaces of the plurality of conductive layers, and the insulating layer is rubbed against the graphene conjugate. a second container that is formed on the second container and a second container that is formed on the second container; a second container that is formed on the second container and a third container that is formed on the second container; a second container that is formed on the second container and a third container that is formed on the second container; a second container that is formed on the second container and a third container that is formed on the second container;a fourth step of simultaneously manufacturing a plurality of circuit components in which an insulating layer and a conductive layer are bonded to the graphene conjugate, the fourth step including a process of simultaneously peeling the graphene conjugate off from the bottom surface of the second container; A method for simultaneously manufacturing a plurality of circuit components, in which the process consisting of the above four steps is carried out in succession, whereby a plurality of circuit components having the same configuration are simultaneously manufactured.
3. The method for forming an insulating layer according to the third step of claim 1 comprises the steps of: The first metal compound which precipitates a metal oxide upon thermal decomposition as described in the third step of claim 1 is an aluminum carboxylate compound, such as aluminum caprylate, aluminum benzoate, or aluminum naphthenate, which precipitates aluminum oxide upon thermal decomposition, and the aluminum carboxylate compound is used as the first metal compound which precipitates aluminum oxide upon thermal decomposition, and a processing method for forming an insulating layer comprising a collection of insulating aluminum oxide fine particles friction-bonded together on the bottom surface of a third container in the shape of the bottom surface according to the processing method described in the third step of claim 1 is provided.
4. The method for forming a conductive layer according to the fourth step of claim 1 comprises the steps of: The second metal compound that precipitates a metal by thermal decomposition described in the fourth step of claim 1 is any one of copper carboxylate compounds consisting of copper octylate, copper laurate, and copper stearate, which precipitate copper by thermal decomposition, and the copper carboxylate compound is used as the metal compound that precipitates copper by thermal decomposition, and a conductive layer consisting of a collection of copper fine particles in which conductive copper fine particles are metallically bonded to each other is formed on the bottom surface of a fourth container in the shape of the bottom surface according to the treatment method described in the fourth step of claim 1.
Citation Information
Patent Citations
Solenoid-operated type fuel injection valve
JP1986066860A
Metal board for semiconductor component and its manufacturing method
JP2004342636A
Shape of mounting metal substrate for LED element and LED element mounting substrate
JP2007158086A